GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2018)
A dataset containing 1013045852 species occurrences available in GBIF matching the query: All data. The dataset includes 1013045852 records from 20864 constituent datasets: 3168 records from Sostenibilidad del uso y manejo tradicional de la palma de guano (Sabal spp, Arecaceae) en el área maya de Yucatán. 327284 records from Fungi (S). 6366 records from Kyoto University Reptile Collection. 4 records from Schizopyga alinae, a genus of pimpline parasitoid wasps (Hymenoptera: Ichneumonidae: Pimplinae) new to the Afrotropical region. 8 records from Ompok argestes, a new species of silurid catfish endemic to Sri Lanka (Teleostei: Siluridae). 319 records from SNH Invertebrate Site Condition Monitoring 2013/14: Cairngorms SSSI. 94 records from New species and records of pollen and sap beetles for Iran (Coleoptera: Kateretidae, Nitidulidae). 42 records from Redescription of two troglobiotic species of Deuteraphorura Absolon, 1901 (Collembola, Onychiuridae) from the Western Carpathians. 44 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 3 records from Revision of the leafhopper genus Soractellus Evans (Cicadellidae: Deltocephalinae) with description of a new species from Pakistan. 819 records from Freshwater Bullhead Survey Data in Wales. 94 records from New species and additional data on the chewing louse genus Myrsidea (Phthiraptera: Menoponidae) from wild Neotropical Passeriformes (Aves). 4 records from First record of Isegama Krombein (Hymenoptera, Chrysididae, Amiseginae) from China, with description of a new species. 40 records from SeaIceMeiofaunaCanadaBasin2002. 42570 records from Bird Collection of Museum and Institute of Zoology PAS. 45321 records from HRCB - Herbário Rioclarense. 3848 records from (Table 7) Miocene to Pliocene nannofossil range chart for ODP Hole 134-832B. 946 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Luberon_2017_12_18. 20403 records from Peces asociados a los arrecifes coralinos del norte de Veracruz. 26 records from Seven new species of the genus Xestoleberis (Ostracoda: Podocopida: Cytheroidea) from the Fiji Archipelago. 162 records from Taxonomic notes and faunistic data on the Muscidae (Diptera) of the Altai Mountains (Russia). 28 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 2380 records from Aves de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 16093 records from RNF - Données de la Communauté de Communes de Gevrey Chambertin. 28410 records from MOSS - Herbário Dárdano de Andrade Lima. 2130 records from Alterra (NL) - Microarthropods inventory in drift sands. 566 records from Non-vascular Plants, Outer Hebrides. 4 records from A new subfamily of Feaellidae (Arachnida, Chelonethi, Feaelloidea) from Southeast Asia. 1442 records from Forest inventory for above ground carbon estimation in Biosphere Reserve of W.. 2372 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 35490 records from Distribution of Lower Plants in Greater Manchester. 7706 records from CHAS Oology Collection (Arctos). 63 records from USGS NRP - Submerged Aquatic Plants - 1966-2009. 2 records from Miriapodi di alcune grotte della Campania. 64370 records from DREAL_PACA_2017_12_18. 6 records from A new species of Polyipnus (Stomiiformes: Sternoptychidae) from the Western South Pacific. 33185 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 1 records from Parathelphusa pardus, a new species of lowland freshwater crab from swamps in central Sumatra, Indonesia (Crustacea: Brachyura: Gecarcinucidae). 26 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 4866 records from Inventario de los crustáceos decápodos asociados al ecosistema coralino de Pocillopora en el Pacífico tropical mexicano. 31452 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 7946 records from SPC PROCFish/C Fish Observations Wallis and Futuna 2005. 382 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 3207 records from Establecimiento de línea base para el monitoreo de especies de plantas de interés para la conservación. 10687 records from Structure and function of contemporary food webs on Arctic shelves: A panarctic comparison. The pelagic system of the Kara Sea- communities and components of carbon flow. 4 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 14 records from A new Eastern Central Atlantic skate Raja parva sp. nov. (Rajoidei: Rajidae) belonging to the Raja miraletus species complex. 2 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 458100 records from RECORD Butterfly Data. 102 records from Colección de Aráceas del Jardín Botánico San Jorge. 2 records from Taxonomic description and 3 D modelling of a new species of myzostomid (Annelida, Myzostomida) associated with black corals from Madagascar. 4 records from ERRATUM: Formal description of Protosticta nigra spec. nov. from Vietnam. 2 records from Hoplophora carinata. 3360 records from Field Study Group of the Dutch Mammal Society (NL) - 2007 - Mammal Survey Estonia. 1 records from Off the scale: a new species of fishscale gecko (Squamata: Gekkonidae: Geckolepis) with exceptionally large scales. 6 records from Description of a new species of Namalycastis (Annelida: Nereididae: Namanereidinae) from the Brazilian coast with a phylogeny of the genus. 334 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto11-19. 4746 records from Observations de Mammifères marins. Globice Réunion 2009-2013. 2 records from Oribates globulus. 409716 records from Vascular Plant Records up to 2010. 1314 records from Caracterización de la avifauna en una zona delimitada entre los municipios de Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nariño). 10800 records from smavd_2017_12_18. 21 records from Solifugae Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 30 records from Additions to the ichthyofauna of the Tristan da Cunha Group, South Atlantic Ocean.. 1 records from Description of a new species of the genus Paecilocaulus Fairmaire (Coleoptera: Anthribidae) from Fiji. 2 records from Tidbinbilla Nature Recording System. 61865 records from HEPH - Herbário Ezechias Paulo Heringer. 7952 records from (Figure 13) Distribution of middle Miocene through middle Pleistocene planktonic foraminifera in ODP Hole 132-810C. 110 records from Tomato French national collection. 82616 records from TPWD HARC Texas Coastal Fisheries San Antonio Bay Trawl. 230 records from Review of East Palaearctic species of Sympycnus Loew, 1857, with a key to species. 3872 records from Reports of New Zealand Flatworms in Scotland, 1989 - 2005. 2363 records from Palynological analysis of sediment core GeoB9508-5. 4 records from Description of male of the rarest European Carpenter-moth Stygioides persephone (Reisser, 1962) (Lepidoptera: Cossidae). 49620 records from Oiseaux nicheurs de France métropolitaine 1985-1989 - nidification probable. 66868 records from Naturalis Biodiversity Center (NL) - Amphibia and Reptilia. 4 records from Nebria (Patrobonebria) incognita n. sp. and Nebria (P.) hiekeiana n. sp., two new species from the Western Himalaya, with remarks on Nebria (P.) desgodinsi (Coleoptera, Carabidae, Nebriinae). 5901 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 2 records from The taxonomic implication of frontal tubercles in Polypedilum subgenera diagnoses, with re-description of Polypedilum isigabeceum Sasa & Suzuki (Diptera, Chironomidae). 4089 records from (Table 22) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-594. 722 records from SEWBReC Lacewings and Allies (South East Wales). 4518 records from Computarización de la Colección de Referencia para Zoología, Arqueozoología y Paleontología del Museo de Historia Natural de la Universidad Autónoma de Baja California Sur. 261 records from Additional list of gregarous Benin valuable species. 89664 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 1757 records from Estudio florístico de las algas marinas de la parte del Golfo de California, México. 4 records from Cirrophorus species (Annelida: Polychaeta: Paraonidae) in the Sea of Marmara, with description of a new species. 6506 records from ISU Birds. 2 records from Pseudotrichonotus belos new species, first record of the fish family Pseudotrichonotidae from Australia (Teleostei: Aulopiformes). 3 records from A new skink of the genus Sphenomorphus Fitzinger, 1843 (Squamata: Scincidae) from Hon Ba Nature Reserve, southern Vietnam. 9330 records from Herpetile collection NTNU University Museum. 2 records from A new species of Cladotanytarsus (Lenziella) from Oregon supports the systematic concept of the subgenus (Diptera: Chironomidae). 5922 records from PINK - Amphibia monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 19195 records from observe_tuna_ecoscope. 313 records from VIP topsoil data jointsampling soilfauna, 2008. 84 records from Taxonomic clarification of the Eumicrotremus asperrimus species complex (Teleostei: Cyclopteridae) in the eastern North Pacific. 702 records from (Table 4) Benthic foraminiferal community at DSDP Hole 94-609B. 700542 records from ARABEL - Arachnologia Belgica. 7557 records from Herbarium specimens of Limoges university (LIMO). 672 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 8 records from Settling the name Diomedea exulans Linnaeus, 1758 for the Wandering Albatross by neotypification. 196 records from Twite national sample survey in the UK in 1999. 6 records from A new species of fan-throated lizard of the genus Sitana Cuvier, 1829 from coastal Kerala, southern India. 2 records from Nothrus biurus. 18741 records from Census of medical plant species of Benin (West Africa) by SOS Biodiversity. 10007 records from Freshwater fishes of the Western Balkans. 6 records from Three new species of Oxysarcodexia Townsend (Diptera: Sarcophagidae) from the Colombian Andes. 51 records from ScoliorhAPis stEPAnovi - new species of sea cucumber from the North-West Pacific (Holothuroidea: Synaptida: Chiridotidae: Taeniogyrinae) and some remarks on the genus ScoliorhAPis. 1578 records from Mollusques terrestres de Mayotte : prospections pour l'inventaire des ZNIEFF. 3 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 866 records from Macroinvertebrate abundance in montane tropical streams of varying land-use, Ecuador. 8062 records from UTEP Invertebrates (Arctos). 918 records from Colección de Entomología - Coleoptera - Chrysomeloidea. 3752 records from Atlas of the Amphibians and Reptiles of Poland. 2 records from A new species of Phyllodytes Wagler, 1830 (Anura, Hylidae) from the Atlantic Forest of southern Bahia, Brazil. 194 records from Macroalgas de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 8864 records from HBRG P.F. Entwistle Insects Dataset. 38 records from Mesozoa collection of National Museum of Nature and Science. 10904 records from Systematic census of the private plantations of the firewood of the Benin .. 33 records from Two new species of Epimelitta Bates from Brazil and a new synonymy in Stenopseustes Bates (Coleoptera, Cerambycidae, Cerambycinae, Rhinotragini). 8 records from On the synonymy of some taxa of the genus Xylena Hübner (Lepidoptera, Noctuidae). 24056 records from UFMT - Herbário UFMT. 5726 records from Invertebrates compiled by W.Block. 48 records from A review of the powderpost beetle genus, Xylopertha Guérin-Méneville, 1845, with a new species and new synonymy (Coleoptera: Bostrichidae: Bostrichinae: Xyloperthini). 4864 records from Black grouse annual lek surveys in Argyll & Bute, 2002-2011. 10786 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 28188 records from White-tailed eagle reintroduction in Scotland, 1975 onwards - Sightings data. 3 records from New Earwigs in Protodiplatyidae (Insecta: Dermaptera) from the Middle Jurassic Jiulongshan Formation of Northeastern China. 192 records from The genus Rosalba Thomson, 1864 (Coleoptera, Cerambycidae, Lamiinae, Apomecynini). 12684 records from AMNH Invertebrate Paleontology Collection. 6000 records from Herbario Virtual Bosques Secos de Colombia - Sección Herbario Universidad de Córdoba (HUC). 18 records from New records of two endemic troglobitic and threatened arachnids (Amblypygi and Opiliones) from limestone caves of Minas Gerais state, southeast Brazil. 2046 records from Poliquetos invasores (Annelida: Polychaeta) del Puerto de Mazatlán, Sinaloa. 486 records from UTEP Fish (Arctos). 12 records from A new species of Synotaxus and the first chromosomal study on Synotaxidae, presenting a rare XY sex chromosome system in spiders (Araneae, Araneoidea). 2578 records from RECORD Orthoptera Data. 4866 records from Inventaire des odonates dans le Parc national des Cévennes. 3926 records from Hypogean macro-Crustacea records. 1429 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 58 records from Nomenclatural and type catalogue of Athoracophoridae (Mollusca: Eupulmonata: Succineoidea): a synopsis of the first 185 years of biodiscovery in the South West Pacific region. 561 records from A review of the genus Prosodes Eschscholtz, 1829 (Coleoptera: Tenebrionidae) of Iran. 4023 records from Plant specimens of Takatsuki Nature Museum (Aquapia Akutagawa). 64 records from Coeroeni/Sipaliwini River Expeditions 1988/1989. 1136 records from Invertebrados y aves playeras de la Laguna Madre de Tamaulipas, México. 417 records from Inventario de Aves en la Finca la Reserva, Yopal, Casanare. 6 records from On Gonorynchus, Gonorhynchus, Gonorinchus, Gonorhinchus and Gonorrhynchus, and some other names of labeonine fishes (Teleostei: Gonorynchidae and Cyprinidae). 5398 records from Parámetros para medir la biodiversidad y su cambio. Análisis ecológico y biogeográfico. 16738 records from Inventaire des Ephémères de métropole (Opie). 5472 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 2 records from Eight species in the Nebela collaris complex: Nebela gimlii (Arcellinida, Hyalospheniidae), a new species described from a Swiss raised bog. 866 records from Guadeloupe_Ignames. 3278 records from Avena wild species collection. (N.I.Vavilov Institute of Plant Genetic Resources (VIR)). 57 records from (Table 1) Rodent (lemming and vole) densities in 5 study areas in the Canadian Arctic. 202 records from MVZ Mammal Observations (Arctos). 114 records from Review of the Japanese Microtendipes tera: Chironomidae: Chironominae), with description of a new species. 93856 records from Canadian Museum of Nature Mammal Collection. 202 records from Results of diatom analysis of Hole 302-M0004A. 213 records from Tejidos de especimenes colectados en la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 1504 records from Species observations during citizen science expeditions. 6124 records from UTEP Birds (Arctos). 882 records from Steuer A. 1939. The fishery grounds near Alexandria. XIX Mollusca. Notes and Memoirs No 33. 14 records from A new species of Alonella Sars, 1862 (Crustacea: Cladocera: Chydoridae) from the Ecuadorian Andes. 4578 records from Specimen records of spiders (Arachnida: Araneae) by monthly census for 3 years in forest areas of Yakushima Island, Japan. 12 records from Dr.Karl Viets. 1935. The fishery grounds near Alexandria. IV. -Some Marine Mites From Alexandria. Notes and Memoirs No 11. Fisheries Research Directorate, Egypt.. 2399 records from Pollen profile RAA37, Lake Racou, France. 13 records from Key to species of the genus Bambusananus Li & Xing (Hemiptera: Cicadellidae: Deltocephalinae), and with description of a new species from China. 19892 records from RECORD Amphibian Data. 3116 records from Base de datos de los pastos marinos mexicanos.. 84 records from DENOMBREMENT SIMULTANE ET SYNCRONISE DES OISEAUX D’EAU MIGRATEURS AU TOGO. 347 records from (Figure 3) Foraminiferal assemblages recovered from DSDP Hole 79-547B. 62 records from Salud coralina de las comunidades arrecifales de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 2 records from A new species of the genus Xya Latreille, 1809 from China (Orthoptra, Tridctyloidea, Tridactylidae). 4 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Conopophagidae. 4560 records from Herbario del Museo Municipal de Historia Natural de San Rafael (MMHNSR), Mendoza. Argentina. 476 records from Revision der europäischen Gattungen und Arten der Familie Brachychthoniidae (Acari, Oribatei) Teil 1. Allgemeiner Teil: Brachychthoniidae Thor, 1934. Spezieller Teil: Liochthonius v. d. Hammen, 1959, Verachthonius nov. gen. und Paraliochthonius nov. gen.. 2 records from Vastarena, a new genus for the New Caledonian cicada Abroma pumila Distant (Insecta: Hemiptera, Cicadoidea, Cicadidae). 1 records from Etmopterus lailae sp. nov., a new lanternshark (Squaliformes: Etmopteridae) from the Northwestern Hawaiian Islands. 408 records from UWIZM Lizards. 76749 records from Insect specimens of Toyama Science Museum. 3808 records from Flickr (01) Shieldbugs & allied species. 1111145 records from BRERC species records within last 15 years. 18 records from Three new species of spinicaudatan clam shrimps from Australia, all from gnammas (rock pools). 164 records from (Table 2) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 20-198A. 394 records from Estudio demográfico y genético de Desmoncus quasillarius Bartlett (Arecaceae). 2 records from Données naturalistes d'Eric DUFRENE. 10 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 135 records from Redescription and new records of Ontholestes brasilianus Bernhauer, 1906 (Coleoptera: Staphylinidae: Staphylininae). 4 records from Osteology and relationships of Libanopycnodus wenzi gen. et sp. nov. and Sigmapycnodus giganteus gen. et sp. nov. (Pycnodontiformes) from the Late Cretaceous of Lebanon. 50 records from A new group of species within the bee genus Ruizantheda, with a revised key to the males of the genus (Hymenoptera: Halictidae: Caenohalictini). 8444 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 7 records from Two new species of Cossinae (Lepidoptera: Cossidae) from Sindh Province of Pakistan. 177 records from Report on the Danish Oceanographical Expeditions 1908-10 to the Mediterranean and adjacent seas- Calcareous Algae. 71395 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 86 records from Studies on Gripopterygidae (Plecoptera) from Espírito Santo State, Brazil. 72 records from Comunidad de Herpetos Presentes en la Ciénaga de Montaño, Municipio del Carmen de Atrato. 45608 records from Muséum d'histoire naturelle de Besançon. 4 records from New species of Victoriopisa Karaman & Barnard, 1979 (Crustacea: Amphipoda: Eriopisidae) from Vembanad backwaters, Southwest coast of India. 15 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 54 records from Black grouse lek survey in Lothian and Borders, 2008. 38916 records from Insect specimens of Komatsu City Museum. 2768 records from Aves en el municipio de Medina (Cundinamarca) y San Juanito (Meta) - Proyecto Colombia Bio. 192 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 16524 records from Observations issues des suivis télémétriques des éléphants de mer dans les TAAF par le CEBC. 13701 records from Herbarium WRSL, Main Collection. 32 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2000. 9186 records from Mamíferos silvestres de la cuenca del río Mezquital-San Pedro, Durango-Nayarit. 19348 records from Free-living marine Nematodes from San Antonio and Cormoranes sandy beaches (Rio Negro, Argentina), 2006.. 78 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 16 records from The spiny theridiid genus Meotipa Simon, 1895 in India, with description of a strange new species with translucent abdomen and a phylogenetic analysis about the genus placement (Araneae, Theridiidae). 5496 records from Grass Collections from Ghana. 220 records from (Appendix G) Benthic foraminifera accumulation rates of ODP Site 167-10121. 1198 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 150 records from (Appendix H) Benthic foraminifera groups in ODP Hole 172-1055B. 328 records from A synopsis of the subgenus Centris (Hemisiella) Moure, 1945 (Hymenoptera: Apidae: Centridini) in Colombia, with description of a new species. 12 records from Synodontis acanthoperca, a new species from the Ogooue River system, Gabon with comments on spiny ornamentation and sexual dimorphism in mochokid catfishes (Siluriformes: Mochokidae).. 29598 records from UESC - Herbário Universidade Estadual de Santa Cruz. 4 records from Diversity of shrews in Ethiopia, with the description of two new species of Crocidura (Mammalia: Lipotyphla: Soricidae). 12 records from An updated and detailed taxonomical account of the large Branchiopoda (Crustacea: Branchiopoda: Anostraca, Notostraca, Spinicaudata) from the Yale North India Expedition deposited in the Yale Peabody Natural History Museum. 9 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 134 records from Taxonomy of the genus Protocypus J. Müller, 1923 (Coleoptera: Staphylinidae: Staphylinini) and two new species from China. 298 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 50998 records from SP-Fungi - Maria Eneyda Pacheco Kauffmann Fidalgo. 10863 records from Millenium Seedbank (MSB). 8 records from Chilopoden und Diplopoden aus Jugoslavischen Höhlen. 102 records from Freshwater Gastropods of Taveuni. 48 records from Six new species of silk-lined burrow spider genus Stenoterommata Holmberg, 1881 (Araneae, Nemesiidae) from southern Brazil. 704 records from Bedfordshire Diplopoda (BNHS) - 1975-1985. 120 records from SuLaMa Galidictis grandidieri occurence data. 688 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Orthoptera (ZUFMS-ORT). 172 records from Checklist of the earthworms (Oligochaeta) of Kerala, a constituent of Western Ghats biodiversity hotspot, India. 14496 records from DBRC Hemiptera species records 1969 to 2015. 1966 records from Embrapa Pecuária Sul - Herbário CNPO. 22004 records from Dataset of Phenology of flora of mediterranean high-mountains meadows (Sierra Nevada). 17 records from Inventaire des Ascidies de Guadeloupe et de Martinique. 866 records from Collection entomologique de Patrick JAUMES (Coléoptères). 7014 records from Flora marina (Clorophyta, Phaeophyta, Rodophyta) y fauna conspicua (Echinodermata, Mollusca, Polychaeta) del Complejo Insular Espíritu Santo-Cerralvo-San José en BCS, México. 4 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 10 records from First record of Pulvinaria urbicola Cockerell (Hemiptera: Coccidae) from India, with a key to the Indian species of Pulvinaria Targioni Tozzetti. 144 records from A revision of the genus Pochytoides Berland & Millot, 1941 (Araneae: Salticidae), with descriptions of six new species. 138638 records from Données de l'Observatoire de la Faune de Bourgogne. 2 records from Bringing taxonomy to school kids: Aedokritus adotivae sp. n. from Amazon (Diptera: Chironomidae). 15 records from On the taxonomy of Lygosoma bampfyldei Bartlett, 1895 (Squamata: Scincidae) with descriptions of new species from Borneo and Peninsular Malaysia and the resurrection of Lygosoma schneideri Werner, 1900. 2484 records from T. L. Hankinson Vertebrate Museum (EMU) Mammal Collection. 696 records from North Marine Region sawfish collection records (DEW collation), Australia (1912 - 2004). 9988 records from SEWBReC Molluscs (South East Wales). 72 records from Nematomorpha from the Philippines, with description of two new species. 1312 records from Diseño, planeación y manejo sustentable de ecoturismo. 735 records from A review of Tersilochinae (Hymenoptera: Ichneumonidae) of Finland. Part 1: taxonomy. 52564 records from Curculionoidea of Poland. 62265 records from pins. 2570 records from Calcareous plankton response to orbital and millennial-scale climate changes from ODP Leg 161-975. 743 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 130-807B. 8912 records from Oiseaux occasionnels de France. 7 records from Grammatonotus brianne, a new callanthiid fish from Philippine waters, with short accounts of two other Grammatonotus from the Coral Triangle. 496 records from Programa regional para la caracterización y el monitoreo de ecosistemas de manglar del Golfo de México y Caribe Mexicano: Veracruz. 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 16 records from Hydrolagus matallanasi sp. nov. (Holocephali, Chimaeridae) a new species of rabbitfish from southern Brazil.. 5 records from New species of Tomocerus (Entomobryomorpha, Tomoceridae) with remarkable form of mucronal dorsal lamella. 13200 records from USAC Mammals Collection. 35 records from Colección de referencia del Laboratorio de Zooarqueología del INAPL (INAPL/LZ). 84 records from (Table 2) Major nannofossil abundances in three Leg 194 site survey gravity cores. 4768 records from Status, distribución, ecología y conservación de las cotorras serranas (Rhynchopsitta pachyrhyncha y R. terrisi) en el norte de México. 14 records from Bythaelurus bachi n. sp., a new deep-water catshark (Carcharhiniformes, Scyliorhinidae) from the southwestern Indian Ocean, with a review of Bythaelurus species and a key to their identification. 1450 records from Sepsidae Recording Scheme - records verified via iRecord. 20434 records from RECORD Aculeate Hymenoptera Data. 714 records from (Figure 10) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-537. 2 records from Japeaeiella dollŋpartoniana, a New Widespread Lichen in the Appalachian Mountains of Eastern North America. 27619 records from Sightings Map of Invasive Plants in Portugal. 6944 records from Vegetation releves in 150 grassland EPs in 2008. 1040992 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 72 records from From Corsica to Britain: new outdoor records of Ocnerodrilidae (Annelida: Clitellata) in western Europe. 26896 records from Beetles (LSM). 6214 records from Diversité et distribution des espèces de plantes menacées au Bénin. 3162 records from Collection of Occurrence data on mammal species during wildlife census in W Biosphere Reserve in 2013 and 2015.. 179652 records from PACA-AGP - Herbarium Anchieta. 436 records from MATRIX project, monkeys near Kampala in Uganda. 17254 records from SJRP-Pteridophyta - Herbário de Pteridophyta de São José do Rio Preto. 1976 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Corynephorus canescens domiated grassland. 56904 records from Mollusc data of Molltax, Norway. 388 records from fauna_do_municipio_de_araraquara-sp. 129 records from Marine Sightings & Miscellaneous species records from Natural Resources Wales (NRW), 2008 onwards. 924 records from Knoydart Lichens, 1990. 2 records from Macrozoque hoplandrioides (Coleoptera: Staphylinidae: Aleocharinae), a new genus and species of false Lomechusini from México. 48 records from Inventarios de Aves de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 4847 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 9 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 105 records from New and little-known species of isopods (Crustacea, Isopoda) from the eastern Mediterranean. 38165 records from SJRP - Herbário de São José do Rio Preto. 73 records from Fossil (JNHM-FO). 127 records from Abyssal fauna of the UK-1 polymetallic nodule exploration area, Clarion-Clipperton Zone, central Pacific Ocean: Mollusca. 20 records from Three new genera and three new species of Nearctic Lasiopteridi (Diptera: Cecidomyiidae: Cecidomyiinae) from Asteraceae and Caprifoliaceae, and the tribe Rhopalomyiini subsumed under Oligotrophini. 4146 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 18 records from The family Hyalidae (Crustacea: Amphipoda: Talitroidea) from Korean waters. 2. Genus Protohyale Bousfield & Hendrycks, 2002. 20797 records from Nijmegen Natural History Museum (NL) - Herbarium. 81 records from Review of the leafhopper tribe Stenometopiini (Hemiptera: Cicadellidae: Deltocephalinae) from China with description of four new species. 41 records from Site Condition Monitoring of Annex II Vertigo species in Scotland. 5774 records from Distribución, abundancia y selección de hábitat de especies de aves amenazadas y en peligro de extinción en los bosques de montaña de Chiapas. 462 records from (Figure 1f) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3175BC. 1445 records from La Planète Revisitée, mission complémentaire entomologique, massif du Mitaraka, août 2015. 326529 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 1 records from Laimosemion leticia (Teleostei: Cyprinodontiformes: Rivulidae), a new species from the upper Rio Amazonas, Southern Colombia. 126 records from Aquatic and semiaquatic Heteroptera (Nepomorpha and Gerromorpha) fauna of Greek holiday islands (Rhodes, Crete and Corfu) with first records of three species from Europe and Greece. 276 records from (Figure 1) Stratigraphic distribution of taxa at DSDP Hole 79-547B. 4 records from A new species of Ubychia Rost, 1893 (Coleoptera: Curculionidae: Brachycerinae) from the island Samos, Greece, with a discussion on the distribution of the genus. 2700 records from ENBI WP 13 Martius C. F. P. von Collection subset (Muenchen). 47277 records from Colección Zoológica de la Universidad del Tolima (CZUT) - Macroinvertebrados. 1200 records from (Table 3) Protist occurrence in bottom sea ice and surface water samples obtained during a CCGS Amundsen cruise in 2007/2008. 18 records from Prosorhynchus Odhner, 1905 (Digenea: Bucephalidae) from the orange-spotted grouper Epinephelus coioides (Hamilton, 1822) (Epinephelidae), including Prosorhynchus tonkinensis n. sp., from the Gulf of Tonkin, Vietnam. 67309 records from RNF - Données de l'association Vivarmor Nature. 489 records from Measurements of elephant tusk trophies taken in Botswana 2002. 1368 records from Inventario de Flora de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Calón y La Osa. Municipios de San Francisco y Sonsón-Antioquia.. 3126 records from JOIw - Xiloteca Joinvillea. 20 records from Phylogenetic analysis of the Neotropical Pristimantis leptolophus species group (Anura: Craugastoridae): molecular approach and description of a new polymorphic species. 53987 records from Marie-Victorin Herbarium (MT) - Bryophytes. 561 records from Revision of the Oriental Genus Physodera Eschscholtz, 1829 (Coleoptera, Carabidae, Lebiini, Physoderina), with the descriptions of two new species. 840420 records from Naturalis Biodiversity Center (NL) - Lepidoptera. 931668 records from Dry Tortugas Reef Visual Census 2010. 6012 records from Computarización del Herbario Ficológico de la Universidad Autónoma de Baja California Sur. 9099 records from Plant specimens of Toyota City Nature Sanctuary (from non-museum circle). 114 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 32511 records from Colección de Insectos de la Universidad del Quindío (CIUQ). 1749 records from Données Rhopalocères de Cistude Nature (Mathieu Molières). 3 records from Description of a new species of the genus Mongolotettix Rehn, 1928 (Orthoptera: Acrididae) from Fujian, China. 2212 records from Zoobenthos data from the Southern Beaufort Sea, 1971-1975. 6 records from Revision of the Nearctic species of Callomyia Meigen (Diptera: Platypezidae) and phylogeny of the genus. 837 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 746288 records from Atlas de las Aves de México: Fase II. 74 records from Checklist, new species and new records of Cerambycidae (Insecta: Coleoptera) from Chapada Diamantina, Bahia state, Brazil. 66908 records from SP-Bryophyta - Maria Eneyda P. Kauffman Fidalgo. 86 records from Relative abundance of planktic foraminifer Globigerinita uvula in sediment core PS1243-1. 12 records from Taxonomy and biology of Simulium clarkei Stone & Snoddy (Diptera: Simuliidae), a poorly known black fly of the southeastern United States. 13896 records from Invertebrates (Type Specimens) of the Swedish Museum of Natural History. 6 records from On the centipedes (Chilopoda) of the Republic of Macedonia. 671 records from Fiocruz/CBAM - Coleção de Bactérias da Amazônia. 8792560 records from Finnish Floristic Database (Finnish Museum of Natural History Collections). 72 records from Norwich Reptile Study Group Records for 2010. 920 records from Insectos recolectados en trampas Malaise en el departamento de Vichada - Proyecto Colombia Bio. 100 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 2844 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 3974 records from DREAL_PACA_-_N2000_-_Office_National_des_Forêts_83_2017_12_18. 2 records from Oppia nitens. 2590 records from (Table T4) Paleocene calcareous nannofossil abundance of ODP Hole 173-1069A. 813 records from Herbario de Plantas Vasculares del Museo Municipal de Ciencias Naturales 'Lorenzo Scaglia' MMPEAAH. 66 records from A new species of Microglanis Eigenmann, 1912 (Siluriformes, Pseudopimelodidae) from rio São Francisco basin, Brazil.. 366 records from Inventaire des Scléractiniaires de la région du Diahot. 942 records from Manual para la identificación de lianas en el campo. 1300 records from Review of Dissomphalus Ashmead (Hymenoptera, Bethylidae) from Panama, with key to the Central American species. 1779 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 192552 records from Entomology collection, UiT. 3 records from Description of a new species of Pinnotheres, and redescription of P. novaezelandiae fBrachyura: Pinnotheridae). 299247 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 45 records from Five new species of Ytu Reichardt (Coleoptera: Myxophaga: Torridincolidae) and new records from Brazil. 94 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Protozoa. 140 records from Porifera Collection - Instituto Nacional de Pesquisas da Amazônia. 132 records from A global revision of the Seahorses Hippocampus Rafinesque 1810 (Actinopterygii: Syngnathiformes): Taxonomy and biogeography with recommendations for further research. 21572 records from Camera trapping bird data. 58 records from Hypostomus velhochico, a new keeled Hypostomus Lacépède, 1803 (Siluriformes: Loricariidae) from the rio São Francisco basin in Brazil. 10 records from Revision of the grassland leafhopper genus Jilinga Ghauri (Hemiptera: Cicadellidae: Deltocephalinae: Paralimnini) with description of a new species from China. 29822 records from Data from EIAs and other studies coordinated by the national forestry authority of Uganda. 213882 records from Countryside Council for Wales - Welsh Peatland Invertebrate Survey (WPIS). 10 records from A new dwarf crayfish (Decapoda: Cambaridae) from floodplain swamps in central Alabama. 84 records from Pseudecheneis suppaetula, a new species of glyptosternine catfish (Teleostei: Sisoridae) from India.. 1978 records from (Table 6) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-590B. 63 records from Five new species of the genus Paromphacodes (Lepidoptera: Geometridae: Geometrinae) from High Andes in Ecuador. 304 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 480 records from Sealife Tracker. 3 records from Description of the larva and pupa of Phileurus truncatus (Palisot de Beauvois, 1806) (Coleoptera: Scarabaeidae: Dynastinae: Phileurini) with a key to described third instars of New World Phileurini. 256 records from Colección del Herbario del Jardín Botánico de la Universidad Nacional de Colombia Sede Caribe. 3680 records from Morandin PhD Thesis / La Crete, Alberta. 1123 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 3900 records from Data from vegetation plots at Atiquipa, Southern Peru. 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 3105 records from ZFMK Diptera collection. 18 records from Contribution to the fauna of the genus Meroplius Rondani, 1874 (Diptera, Sepsidae) of the Australasian / Oceanian region. 346 records from Measurements of elephant tusk trophies taken in Botswana 2005. 477 records from (Table 2) Occurrence and estimated abundance of planktonic foraminifers at DSDP Hole 85-571. 2 records from Zetes lucorum. 32 records from Land flatworms (Platyhelminthes, Geoplanidae) of São Tomé: a first account on their diversity, with the description of five new species. 1748 records from The Living Murray Fish data. 3 records from Scutellista caerulea (Fonscolombe, 1832) (Hymenoptera: Pteromalidae), new to New Zealand for the second time!. 105 records from Descriptions and synonymies in American Desmiphorini (Coleoptera, Cerambycidae, Lamiinae). 2832 records from Situación actual de ocho especies de anfibios en categoría de riesgo en Veracruz. 35 records from New genera, species and records of Doryctinae (Hymenoptera: Braconidae) from Brazil. 4 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 94 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 7560 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 4386 records from Estado actual de la distribución de los anfibios y reptiles de la Región de Los Tuxtlas. 4 records from Heleniella helvetica sp. n., a cold stenothermic species inhabiting the upper Rhône catchment in central Switzerland [Diptera, Chironomidae, Orthocladiinae]. 174 records from Description of Almafuerte, a new genus of ground spiders from South America (Araneae, Gnaphosidae). 195 records from (Table 12) Distribution of coccoliths in bottom sediments along Core AMK7-653 from the Tajura Rift. 2 records from Die Gattung Carabodes C. L. Koch 1836 in der schwedischen Bodenfauna (Acar. Oribat.). 139 records from Tab. 6: Relative Abundanz einzelner Arten der Endofauna. 61 records from Alien Species in Poland - Plants. 10111 records from Taiwan Fisheries Research Institute – Digital archives of coastal and offshore specimens. 6 records from A new erythroneurine leafhopper genus and species from Thailand (Hemiptera: Cicadellidae: Typhlocybinae). 5445 records from Inventarios de flora y fauna en el piedemonte de los municipios Aguazul, Tauramena y Yopal del departamento de Casanare. 3188 records from (Table 6) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-852B. 2 records from Two new species of Halictophagidae (Insecta: Strepsiptera) including the first record of genus Coriophagus Kinzelbach from India. 296 records from (Table 4) Live benthic foraminifera in sediment core SO130-242MC. 18 records from New species of Hammerschmidtiella Chitwood, 1932, and Blattophila Cobb, 1920, and new geographical records for Severianoia annamensis Van Luc & Spiridonov, 1993 (Nematoda: Oxyurida: Thelastomatoidea) from Cockroaches (Insecta: Blattaria) in Ohio and Florida, U. S. A.. 143 records from Brachypterous ground beetles of the Trichotichnus subgenus Bottchrus Jedlička (Coleoptera, Carabidae) from the Himalaya, with description of fifteen new species. 330 records from Diversidad florística y estado de conservación en dos ventanas de paisaje de la UPR Tunjuelo priorizadas: Usme y Ciudad Bolivar, Bogotá. 21 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Sichuan, Southwest China. 1296 records from Plant specimens of the Museum of Yamagata University. 1365 records from Inventario herpetofaunístico del noroeste de Hidalgo. 13056 records from Xerces Society - Bumble Bee Watch. 12 records from A new species of Angaeus from Malaysia with possible affinity to related genera within Stephanopinae (Araneae: Thomisidae). 2770 records from Countryside Council for Wales - Amphibian & Reptile Licence Return Data. 3038 records from Natura 2000 Vallée de l'Esch, d'Ansauville à Jézainville. 1069 records from UWIZM Local Lepidoptera Collection. 124354 records from LSUMZ Bird Tissues. 4176 records from Rasgos funcionales de plantas, anfibios y aves de estudios bióticos en el Complejo de Páramos Chingaza. 8 records from New data on Synaphosus (Araneae: Gnaphosidae) from Southeast Asia. 10 records from Colaspis caligula, a new species found in association with Vitis vinifera (L.) crops in Argentina (Coleoptera: Chrysomelidae). 106807 records from Naturalis National Natural History Museum (NL) – Invertebrate specimens from marine expeditions. 1218 records from Countryside Council for Wales - Bat Roosts Database- South Wales. 44 records from Remarks on the genus Tamdaotettix Gorochov, 1998 (Orthoptera: Rhaphidophoridae: Aemodogryllinae) from China. 34 records from A stonefly species extinct in Europe (Taeniopteryx araneoides Klapalek, 1902, Taeniopterygidae, Plecoptera) is thriving in the Irtysh River in West Siberia and North Kazakhstan. 18 records from New Oriental genera in the family Issidae (Hemiptera: Fulgoromorpha). 13 records from First finding of anchialine and submarine cave dwelling brittle stars from the Pacific Ocean, with descriptions of new species of Ophiolepis and Ophiozonella (Echinodermata: Ophiuroidea: Amphilepidida). 2 records from A new species of Anheteromeyenia (Porifera, Demospongiae) with an emended diagnosis of the genus. 8 records from Two new species of Amphinemura (Plecoptera: Nemouridae) from the Gaoligong Mountains of Yunnan, China. 2442 records from (Table T14) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones P4a-P6a. 13 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 4210 records from Acari Collection - Instituto Nacional de Pesquisas da Amazônia. 48 records from A Novel Reproductive Mode in Frogs: A New Species of Fanged Frog with Internal Fertilization and Birth of Tadpoles. 5556 records from SPC CoFish Fish Observations Cook Islands 2007. 1512 records from Dieta y preferencias alimenticias de poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en Paz de Ariporo, Casanare. 9618 records from NCC Berkshire Grassland Survey 1984-1987. 32948 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 2 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 1 records from A new Cernosvitoviella species (Clitellata: Enchytraeidae) and its comparison with other Cernosvitoviella species from Sphagnum mires in Hungary. 8169 records from Autoecología de las lagartijas de arena Uma paraphygas y Uma exsul (Sauria: Phrynosomatidae) en las dunas del Bolsón de Mapimí. 150 records from New data on winter crane flies (Diptera: Trichoceridae) of Korea with description of a new species. 27124 records from LERN Invasive Non-native Species Records. 278 records from Taxonomic revision of the genus Bolivaritettix Günther, 1939 (Orthoptera: Tetrigoidea: Metrodorinae) from China, with the descriptions of two new species. 61754 records from MSB Amphibian and Reptile Collection (Arctos). 7252 records from ZUEC-CLB - Coleção de Collembola do Museu de Zoologia da UNICAMP. 260 records from (Table 3) Globorotalia puncticulata, Globorotalia inflata, and their intergrades at DSDP Hole 80-548. 309827 records from SEEE - Diatomées. 36 records from ClassII-peroxidase-sequences_from_pure_cultures_from_HAI. 17 records from A new genus and new species of Edessinae (Hemiptera: Heteroptera: Pentatomidae). 206 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Thamnophilidae. 2382 records from Macroarthropods, Narsarsuaq 2014, Greenland. 36 records from On the brink of extinction: two new species of Anomaloglossus from French Guiana and amended definitions of Anomaloglossus degranvillei and A. surinamensis (Anura: Aromobatidae). 12 records from Leptobotia bellacauda, a new species of loach from the lower Yangtze basin in China (Teleostei: Cypriniformes: Botiidae). 145070 records from Lichen herbarium, UiB. 3 records from A new Indian record and morphological variation for Eulimnadia khoratensis Rogers et al., 2016 (Crustacea: Branchiopoda: Spinicaudata). 6 records from Lavellodrilus notosetosus sp. nov. (Annelida, Crassiclitellata, Acanthodrilidae): a new Mexican earthworm with uncommon characters, revealed by a preliminary revision of subfamily Acanthodrilinae. 22 records from New species of Dichogaster Beddard, 1888 (Clitellata: Benhamiidae) with additional records of earthworms from Guadeloupe (French West Indies). 110 records from Additions and corrections to the systematics of mayfly species assigned to the genus Callibaetis Eaton 1881 (Ephemeroptera: Baetidae) from South America. 2863 records from Hare Survey of Ireland 2006 & 2007. 1287 records from Xiloteca del IANIGLA (IANIGLA-CCT CONICET Mendoza): XIAM.. 1810 records from 2003-2004 Wokingham WHS Surveys. 9730 records from RAVON (NL) - Network Ecological Monitoring Reptiles. 210 records from Conocimiento integral del tapir (Tapirus bairdii) y el pecari de labios blancos (Tayassu pecari) en México. 30 records from Re-definition and review of the Oriental genus Hexachaetus Chaudoir, 1871 (Coleoptera: Carabidae: Orthogoniini). 403 records from (Appendix A) Relative abundance of Emiliania huxleyi in sediment cores of the North Atlantic. 1210892 records from Natural England Marine Monitoring surveys. 6 records from Amended diagnosis and redescription of Pristimantis marmoratus (Boulenger, 1900) (Amphibia: Craugastoridae), with a description of its advertisement call and notes on its breeding ecology and phylogenetic relationships. 2 records from A new species of Chaetozone (Polychaeta, Cirratulidae) from the Bay of Biscay offshore France, together with a review of Chaetozone species from the North Atlantic and adjacent waters. 1007 records from Données naturalistes de Romaric LECONTE. 878 records from Censo del Zarapito Trinador (Numenius phaeopus) y Otras Aves Acuáticas en el Parque Nacional Natural Sanquianga. 6014 records from UCDavis - Western USA - Monarch Butterflies - 1892-2005. 1620450 records from Tercer Inventario Forestal Nacional. Ministerio de Agricultura, Alimentación y Medio Ambiente (España/Spain). 3 records from A new species of the Australian genus Clinopsocus New from coastal California (Psocodea: ‘ Psocoptera’: Elipsocidae). 7455 records from Museum TwentseWelle (NL) - Fossil Sponges Collection. 385 records from (Table AT4) Planktonic foraminiferal stratigraphy of ODP Hole 182-1128C. 40 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 1268390 records from Florida Keys Reef Visual Census 2006. 31251 records from International Fossil Shell Museum (NL) - Mollusca Collection. 1848 records from (Figure 5) Planktonic foraminifera distribution in ODP Hole 101-628A. 384 records from ENBI-Dataset of GART-GloBIS. 82 records from Revision and phylogeny of the Caribbean weevil genus Apotomoderes Dejean, 1834 (Coleoptera, Curculionidae, Entiminae). 45 records from Inventario de Herpetología Buenos Aires, Tauramena, Casanare. 1374 records from Barley French National Collection. 4 records from The identity of Calliphora bezzii Zumpt, 1956 (Diptera, Calliphoridae). 288 records from (Table T1) Benthic foraminifer abundance of ODP Hole 210-1276A sediments. 50 records from A review of subtribe Cymindidina Laporte, 1834 (Coleoptera: Carabidae: Lebiini) in Southwestern Saudi Arabia, with descriptions of two new species. 24983 records from Computarización de la base de datos del Banco Nacional de Germoplasma Vegetal - Fase 2. 1598 records from Calcareous nanofossils in late Pliocene sediments of ODP Site 162-982. 7300 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 6 records from A new highly troglomorphic Loxosceles (Araneae: Sicariidae) from Brazil. 12 records from Description of two new species of the genus Pentacentrus Saussure from China (Orthoptera: Gryllidae). 107 records from A synopsis of the genus Dorcasta Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Apomecynini). 799443 records from South Australian Museum Australia provider for OZCAM. 3596 records from Insect (KIDR-IN). 1970 records from Forest edible fruits from Cameroon. 249 records from Systematic revision of the Potamotrygon scobina Garman, 1913 species-complex (Chondrichthyes: Myliobatiformes: Potamotrygonidae), with the description of three new freshwater stingray species from Brazil and comments on their distribution and biogeography. 8 records from A new platygastrid wasp from Florida (Hymenoptera: Platygastridae).. 21 records from Description of five new coral associated Barnacles of the genus Trevathana (Balanomorpha: Pyrgomatidae) in Pacific Waters. 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 122 records from COA Herpetology Collection (Arctos). 2 records from First report on Paratischeria from Asia (Lepidoptera: Tischeriidae). 150 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 506 records from PSUZC-Mammal Collection. 130 records from Systematics and biogeography of Cuban porcelain crabs (Decapoda: Anomura: Porcellanidae). 39 records from Navigator, a new endemic genus of Cetoniinae (Coleoptera: Scarabaeidae) from Australia, with descriptions of two new species and behavioural studies. 204 records from ZUEC-HOL - Coleção de Holothuroidea do Museu de Zoologia da UNICAMP. 6 records from First description of the female Elimaea melanocantha (Walker, 1869) (Orthoptera: Tettigoniidae: Phaneropterinae) from India. 263 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 323-U1341. 1920 records from HBRG Highland Seashore Project Dataset. 20543 records from CPAP - Herbário CPAP. 1 records from Description of the first new species of Leuctridae (Plecoptera) from Jiangsu Province of China. 21 records from Vietelmis jablonskii, a new species of riffle beetle from Laos and Thailand and new faunistic records on Vietelmis Delève, 1968 from Malaysia (Coleoptera: Elmidae). 4 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 9 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 10 records from New records of the East-Asian Nemoura species (Plecoptera: Nemouridae) for South of the Russian Far East with description of the larvae. 480 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 465 records from Colecta de maíces nativos en regiones estratégicas de la Península de Yucatán. 3001030 records from Centre for Biodiversity Genomics - Canadian Specimens. 6 records from Latheticomyia Wheeler (Diptera: Pseudopomyzidae) from Peru: new species, description of the male of L. longiterebra Hennig and a key to species. 180 records from Review of the tribe Helconini Foerster s. s. from China, with the description of 18 new species. 429 records from Amblypygi Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 160 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 741692 records from Atlas des plantes vasculaires de Lorraine. 48774 records from Angelo State Natural History Collections (ASNHC) - Mammalogy Collection. 21 records from Mastofauna presentes en la ciénaga de Guineo, Riosucio, Chocó. 8 records from new species of Miogryllus Saussure, 1877 and new record of Miogryllus piracicabensis Piza, 1960 (Orthoptera: Gryllidae) from State of Rio Grande do Sul, Brazil, with calling song and chromosome complement. 22978 records from PACA-Fungi - Herbarium Anchieta - Fungi Rickiani. 1380 records from Fishes of the flooded savannas of Paz de Ariporo, Meta River, Orinoco basin. 45 records from Taxonomic notes on Exetastes fukuchiyamanus Uchida, 1928 (Hymenoptera, Ichneumonidae, Banchinae), with description of a new species from Japan and China. 170400 records from CUMV Bird Collection. 6264 records from Publicación de la obra: American species of Acacia (Leguminosae; Mimosoideae). 108 records from Fishes from Madagascar Reef, Campeche Bank, México. 3 records from Revision of the genus Celebargiolestes Kennedy, 1925 (Odonata: Argiolestidae). 381 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 45 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Fannich Hills SSSI. 1841368 records from Données d'occurrences Espèces issues de l'inventaire des ZNIEFF. 1044 records from RV Investigator Voyage IN2016_V06 Seabird Observations, Australia (2016). 6 records from A new species of freshwater crab of the genus Oziotelphusa Müller, 1887 (Crustacea: Decapoda: Brachyura: Gecarcinucidae) from Tamil Nadu, southern India. 10587 records from A dataset from bottom trawl survey around Taiwan. 66288 records from CMNH Birds Collection. 165606 records from NE Scotland fungus and lichen records 1800-2010. 805559 records from CAS Botany (BOT). 224432 records from Some Plant Specimens from PE Herbarium in China from 1900 to 1950. 48769 records from Flora of the Stołowe Mts.. 12 records from Two new sympatric troglobitic freshwater flatworms (Platyhelminthes: Dugesiidae) from a hotspot of subterranean biodiversity in the Neotropics. 2 records from Hongiella marincola sp. nov., isolated from sea water of the East Sea in Korea. 10 records from Taxonomy of Rufocumbre gen. nov., a new Moncini skipper genus (Lepidoptera: Hesperiidae: Hesperiinae). 580032 records from Western Australia Bird Surveys (1987-2015). 3 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 819 records from Crustáceos malacostracos de la cuenca del río Papaloapan, Veracruz. 118 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 6331554 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 60 records from Six new species and new records of the spider genus Chrosiothes from Brazil with the description of the female of Chrosiothes venturosus Marques & Buckup, 1997 (Araneae, Theridiidae, Spintharinae). 1584 records from Registro de vertebrados durante el fototrampeo del convenio 027 - 2014 CVC - Panthera. 21 records from New species and new records of ground spiders (Araneae: Gnaphosidae) from Cyprus. 128937 records from The census of national forest of Benin .. 39 records from Mammal specimens of Toyota City Nature Sanctuary. 190 records from Monografía de los poliquetos (Annelida: Polychaeta) de Quintana Roo, Caribe Mexicano. 5979 records from Inventario de macroalgas de Isla Guadalupe, México. 1076 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Tuluá, Valle del Cauca. 264 records from (Table 4) Relative abundances of benthic foraminifera in ODP Hole 128-799B. 501099 records from The Taiwan Breeding Bird Survey Data. 732 records from Anfibios y reptiles de la cuenca alta y media del río Bita, Vichada (Colombia). 30 records from Review of the Palearctic Atemelia Herrich-Schäffer (Lepidoptera, Yponomeutoidea, Praydidae), with description of a new leafmining species. 1220 records from Farmland bird database in Dumfries and Galloway, 1999-2011. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Taiwan, with keys to all 13 species of the Simulium varicorne species-group. 155256 records from Oiseaux nicheurs de France métropolitaine 1985-1989 - nidification certaine. 8 records from A survey of East Palaearctic Lycosidae (Araneae). 12. Two new Mongolicosa species from Mongolia. 28 records from New records of lampriform fishes (Teleostei: Lampriformes) from the Pacific coast of lower Central America, with comments on the diversity, taxonomy and distribution of the Lampriformes in the eastern Pacific Ocean. 21273 records from UK Roadkill Records. 1300 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Anatidae. 120 records from Mamíferos de dos procesos para la conservación de relictos de bosque seco de la cuenca media – baja del Río Meléndez para la declaratoria de un Área Protegida Pública y para la Consolidación del SIMAP y fondo del agua de Cali. 46 records from Taxonomic studies of Japanese Formicidae part 3: genus Vollenhovia.. 57542 records from Records from the NIWA AllSeaBio marine biology database. 141 records from (Table 3) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-800A. 45366 records from Museu Paraense Emilio Goeldi - Araneae Collection. 7108 records from Museu Paraense Emílio Goeldi - Crustacea Collection. 22698 records from RNF - Données du Syndicat de Gestion des Gorges de l'Ardêche. 794 records from Inventaire National du Patrimoine Naturel : CBN Alpin de Gap. 156005 records from Acoustic monitoring data of avian species inside and outside the evacuation zone of the Fukushima Daiichi power plant accident. 45 records from Halosaur fishes (Notacanthiformes: Halosauridae) from Atlantic Spanish waters according to integrative taxonomy. 93814 records from Sistematización del Herbario Nacional Forestal Biól Luciano Vela Gálvez. 2684 records from Kurzflügler_Raw1. 264 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fringillidae. 9 records from Helobdella buzz n. sp. (Clitellata: Hirudinida), a bromeliad leech from the Brazilian Atlantic Forest. 360 records from (Table 1) Late Maastrichtian calcareous nannofossils in DSDP Hole 22-212. 12 records from Description of a new Episemion species (Cyprinodontiformes: Nothobranchiidae) from northern Gabon and southeastern Equatorial Guinea.. 596 records from Measurements of elephant tusk trophies taken in Botswana 2012. 28 records from First record of Psilacrum Becker 1912 (Chloropidae, Diptera) from Brazil, with the description of a new species. 9 records from Four new species of Epacanthion Wieser, 1953 (Nematoda: Thoracostomopsidae) in intertidal sediments of the Nanji Islands from the East China Sea. 10 records from Schistura larketensis, a new cavernicolous fish (Teleostei: Nemacheilidae) from Meghalaya, Northeast India. 12484 records from Natural history museum data on Canadian Arctic marine benthos. 1382 records from Black grouse national surveys. 180 records from Données naturalistes de Pascal Dupont. 3 records from Mammalia (SMNH-MM). 603 records from Occurrence data of Prytanomyia (Diptera: Asiloidea: Asilidae). 75838 records from Données naturalistes de Xavier CUCHERAT. 235282 records from Marine invertebrate collection NTNU University Museum. 1569 records from Programme Ecoscope: données d'observations des écosystèmes marins exploités. 18528 records from Loup 2010 présence régulière communale (réseau Loup-Lynx ONCFS). 8 records from Zwei neue Arten der Oribatiden-Gattung Nanhermannia. 30 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 1995. 10142 records from Données de mammifères enregistrées dans BazNat - Lot 2. 4 records from Polypedates smaragdinus Blyth, 1852 - a senior subjective synonym of Rhacophorus maximus Günther, 1858. 1 records from First record of the genus Oxyrrhexis Foerster, 1869 (Hymenoptera: Ichneumonidae: Pimplinae, Ephialtini) for the fauna of Egypt, with an unexpected new host record. 3330 records from Colección Ictiológica de la Universidad Industrial de Santander. 5452 records from NPWS Seal Database. 1702 records from (Figure 2d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3245. 24 records from Clarias insolitus, a new species of clariid catfish (Teleostei: Siluriformes) from southern Borneo.. 305 records from New distributional data on aquatic and semiaquatic bugs (Hemiptera: Heteroptera: Gerromorpha & Nepomorpha) from South America. 12 records from Two new species of Loboschiza from Cambodia and Vietnam (Lepidoptera: Tortricidae: Olethreutinae: Enarmoniini). 7 records from Wrapped in flames: Corydoras hephaestus, a new remarkably colored species from the Rio Madeira basin (Teleostei: Callichthyidae). 35426 records from NCSM Mammals Collection. 8 records from Three species of Hydrobaenus Fries (Diptera: Chironomidae: Orthocladiinae) from Belarus. 18 records from Diaphoromyrma, a new myrmicine ant genus (Hymenoptera: Formicidae) from North Eastern Brazil. 22 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 14 records from Two new species of Trimma (Pisces; Gobiidae) from Fiji, south-western Pacific Ocean. 18919 records from Invasive species - American bullfrog (Lithobates catesbeianus) in Flanders, Belgium. 8 records from Two new species of the genus Loboschiza Diakonoff, 1968 (Lepidoptera: Tortricidae: Olethreutinae) from Thailand. 6168 records from DREAL_PACA_-_N2000_-_Office_National_des_Forêts_05_2017_12_18. 56 records from Halophila stipulacea in the Caribbean Sea. 6 records from New Tanytarsus van der Wulp from the Brazilian Amazonia indicate clues to intrageneric relations (Diptera: Chironomidae). 20 records from New species of Zenoria Mulsant (Coleoptera: Coccinellidae) from Brazil and Peru. 2 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 450 records from A preliminary checklist of the skippers (Rhopalocera: Hesperiidae) of Guangxi, China. 10512 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 699 records from Censo abundancia de aves en los Parques Nacionales Naturales de Bahía Malaga, Portete y Old Providence. 960 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 8 records from A new species of Miogryllus Saussure, 1877 and new record of Miogryllus piracicabensis Piza, 1960 (Orthoptera: Gryllidae) from State of Rio Grande do Sul, Brazil, with calling song and chromosome complement. 104904 records from Natagriwal ; Observations made from operations within Natura 2000 habitats and other semi-natural areas. 5856 records from Vascular plant specimens of Shirakami Institute for Environmental Science, Hirosaki University. 2972 records from Inventaire entomologique standardisé des ZNIEFF de Martinique, protocole utilisé de 2011 à 2013. 2560 records from HFSL-Fungos - Herbário Dr. Ary Tupinambá Penna Pinheiro - Fungos. 4 records from Sydney Flatwing (Austroargiolestes isabellae) mating in the wheel position. 100 records from Caledonian Conservation Ltd Incidental Records 2014 onwards. 701 records from SEWBReC Worms (South East Wales). 150285 records from Fungi of Costa Rica (INBio). 58 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 1132 records from Registros de la Caracterización de vegetación y flora del POMCA de la SZH Cuenca del Río Tapias y Otros Directos al Cauca. 1930 records from Norwegian freshwater lake fish inventory. 102000 records from TPWD HARC Texas Coastal Fisheries Matagorda Bay Bag Seine. 26 records from Two new, brachypterous Limnellia species from the Venezuelan Andes (Diptera: Ephydridae). 80940 records from Living Collection of the Gothenburg Botanical Garden. 141397 records from Wikiplantbase #Sardegna. 566 records from Incidental Livistona lanuginosa records. 2 records from Review of subterranean Quedius, with description of the first hypogean species from the Russian Far East (Coleoptera: Staphylinidae: Staphylinini). 132 records from New species of chitons of the superfamily Cryptoplacoidea (Mollusca: Polyplacophora) from Vietnamese waters. 5 records from A new species of Microdeutopus, M. periergos sp. nov. (Crustacea, Amphipoda, Senticaudata, Aoridae) from Cyprus (East Mediterranean Sea). 142 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 338 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 10856 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 22286 records from NBMB Herps. 206 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM6. 2 records from Zetes dorsalis. 50068 records from Canadian Museum of Nature Fossil Vertebrate Collection. 16 records from New data on the Opheliidae (Annelida) from Lizard Island (Great Barrier Reef, Australia): five new species of the genus Armandia Filippi, 1861. 5401 records from Catálogo de los mamíferos de México en resguardo de The Natural History Museum (London), Inglaterra. 17508 records from Propuesta para sistematizar la colección palinológica de polen reciente y fósil del IGLUNAM. 18 records from Review of the genus Pachyanthrax François (Diptera: Bombyliidae) from Egypt, with description of two new species. 18528 records from Big Island Invasive Species Committee - Pest Reports - 2005-2010. 219 records from Taxonomic review of the species of Helina R. - D. (Diptera: Muscidae) from Andean-Patagonian forests. 12 records from Two new species of Tardigrada (Eutardigrada: Ramazzottiidae, Macrobiotidae) from the supralittoral zone of the Atlantic Iberian Peninsula rocky shores. 8 records from The state of systematics of North American Baetis Leach, 1815 (Ephemeroptera: Baetidae), with recommendations for identification of larvae. 2 records from Ueber eine noch nicht beschriebene Nothrus-Art. 2327 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 1. 8 records from New littoral mite species (Acari, Oribatida, Fortuyniidae) from the Galápagos archipelago, with ecological and zoogeographical considerations. 99 records from New species of Brachiacantha Dejean, 1837 (Coleoptera: Coccinellidae) from Mexico and Central America. 5763 records from Abundances indices and biological traits of juvenile salmon sampled in the Nivelle river (France). 83334 records from National Museum of Natural Science. 16 records from Pristimantis antisuyu sp. n. and Pristimantis erythroinguinis sp. n., two new species of terrestrial-breeding frogs (Anura, Strabomantidae) from the eastern slopes of the Andes in Manu National Park, Peru. 234865 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 334 records from DIRMED_2017_12_18. 4618 records from BV Insectarium Virtual. 8192 records from Données naturalistes de Fabien LE NOUVEL. 110 records from Revision of the soft scale genus Paralecanium (Hemiptera: Coccomorpha: Coccidae) with the introduction of three new genera and twenty new species. 20 records from Diglotta mersa (Haliday) and Halobrecta flavipes Thomson, two new species for the Canadian fauna (Coleoptera, Staphylinidae, Aleocharinae). 5526 records from Ecología y genética poblacional de la ballena gris Eschrichtius robustus en la Península de Baja California. 34327 records from Algae herbarium, NTNU University Museum. 2554 records from Museu Paraense Emílio Goeldi - Chelonia Collection. 45 records from Free-living nematodes of the genus Syringolaimus de Man, 1888 (Nematoda, Enoplida, Ironidae) from the Angola Basin, South-East Atlantic Abyss. 459 records from Indian Ocean Islands - Historic Freshwater Aquatic Insect Taxa. 53492 records from Collection Paleontology - GPIT. 17 records from New Pycnomerus Erichson (Coleoptera: Zopheridae: Pycnomerini) from Rimatara, French Polynesia. 3015 records from Computarización de la Colección Paleontológica de la Secretaria de Medio Ambiente, Vivienda e Historia Natural, del estado de Chiapas. 24 records from (Table T1) Coral taxa and their ecological significance in ODP Site 194-1196 and Hole 194-1199A sediments. 18 records from More transcontinental mislabeling in the genus Onthophagus: d’Orbigny’s “ African ” Group 27 (Coleoptera: Scarabaeidae: Scarabaeinae). 10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 95 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 8 records from New fossil taxa of Ischalia Pascoe (Coleoptera: Ischaliidae) from Eocene Baltic amber. 10275 records from Opiliones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 239 records from Données naturalistes de Pauline BALDUCCI. 1 records from The type material of Gryllotalpidae Leach, 1815 (Insecta: Orthoptera: Ensifera) deposited in the Orthoptera collection of the Academy of Natural Sciences of Drexel University, Philadelphia (ANSP): an updated checklist. 29 records from Porcupine Ray Hunt Data. 4 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 219 records from Data on cetacean strandings on the Ukrainian coast of the Black Sea (2017). 392 records from Expédition Karubenthos 2012 : inventaire des Echinodermes de la Guadeloupe. 134 records from Further records on the plant bug tribe Hallodapini (Hemiptera: Heteroptera: Miridae: Phylinae) in Asia, with proposition of two new species and a new synonymy. 42 records from The species group Amabilis of the genus Euplocania Enderlein (Psocodea: Psocomorpha: Ptiloneuridae). 6 records from A new Costa Rican species of Leptanilloides (Hymenoptera: Formicidae: doryline section: Leptanilloidinae).. 4488 records from SPC PROCFish/C Invertebrates Observations New Caledonia 2003 to 2008. 1 records from Nososticta nicobarica sp. nov. (Odonata: Platycnemididae: Disparoneurinae) from Great Nicobar Island, India. 4 records from Mayflies of the Caucasus Mountains. IV. New species of the genus Nigrobaetis Novikova & Kluge, 1987 (Ephemeroptera, Baetidae) from Georgia. 93 records from SNH Invertebrate Site Condition Monitoring 2015: Lindean Reservoir SSSI. 640 records from NMU Bird Collection (Arctos). 2 records from A second new species of Nanophyllium Redtenbacher, 1906 from the northern coast of New Guinea (Phasmida, Phylliidae). 8364 records from Catálogo digital y clave ilustrada de los mosquitos (Diptera: Culicidae) de las zonas áridas de los estados de Nuevo León y Tamaulipas, México. 1226 records from DBG Chatfield Farms Riparian Restoration Ground Vegetation Monitoring. 19653 records from Paleontological Research Institution Collections. 755204 records from Geneva Herbarium – General Collection (G). 13800 records from E. C. Smith Herbarium (ACAD) - Nova Scotia Museum of Natural History. 9918 records from SGHN - Biota Galicia. 3009 records from Abundancia, distribución y estado de conservación de Guaiacum sanctum L. en México. 50 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanterriidae).. 83236 records from Données naturalistes de Pierre JAY-ROBERT. 5287 records from Protected species bycatch in New Zealand fisheries. 982 records from Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 236 records from Generic key and catalogue of Mymaridae (Hymenoptera) of Mexico. 8 records from Camptopoeum (Camptopoeum) baldocki spec. nov., a new panurgine bee species from Portugal and a description of the male of Flavipanurgus fuzetus Patiny (Andrenidae: Panurginae). 5110 records from Biodiversidad de macroinvertebrados bénticos de la región marina Tijuana-Ensenada Baja California, México. 2108 records from Aves de la cuenca alta y media del río Bita, (Vichada) Colombia. 4 records from Syngnathus chihiroe, a new species of pipefish (Syngnathidae) from southern Japan. 31212 records from 2005 - Ongoing United Kingdom MarLIN Shore Thing timed search results. 329917 records from USGS PWRC - Native Bee Inventory and Monitoring Lab (BIML). 15 records from Four new species of the genus Philanthaxia Deyrolle, 1864 (Coleoptera: Buprestidae: Thomassetiini). 28920 records from Carabidae of Poland. 132 records from Mammals (KIEE-MM). 125653 records from Insects from light trap (1992–2009), rooftop Zoological Museum, Copenhagen. 417 records from Australian Sea Lion and New Zealand Fur Seal Distribution Database from Coastal and Marine Resources Information System (CAMRIS). 2 records from A new species of Anthiadinae (Teleostei: Serranidae) from São Pedro and São Paulo Archipelago, Brazil, Equatorial Atlantic.. 15 records from Discovery of representatives of the family Nicoletiidae (Insecta: Zygentoma) from caves of Iran, with descriptions of two new supraspecific taxa. 7497 records from Leicestershire and Rutland Reptile Records to 2011. 513 records from Nematode abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 69 records from UWIZM Turtles and Crocodilians. 44 records from Two new whiprays, Maculabatis arabica sp. nov. and M. bineeshi sp. nov. (Myliobatiformes: Dasyatidae), from the northern Indian Ocean. 16 records from Mamíferos de un Área Degradada por Actividad Minera en la Costa Caucana. 38 records from Three new species of Microbrotula (Teleostei: Ophidiiformes: Bythitidae) from the Indo-West Pacific.. 42 records from Revision of the genus Afrosmicronyx Hustache (Coleoptera, Curculionidae, Curculioninae). 4185 records from Diptera Collection of Museum and Institute of Zoology PAS. 1434 records from Alterra (NL) - Microarthropods inventory in militairy zone Leusderheide. 9386 records from Fiocruz/CCER - Coleção de Ceratopogonidae. 18 records from First record of the monotypic genus Acanopsilus Kieffer, 1908 (Hymenoptera: Diaprioidea: Diapriidae) from the Eastern Palaearctic region. 26613 records from (Appendix 4) Distribution of benthic foraminifers, living, dead, and total assemblage counts, and faunal diversity in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 12556 records from ZMMU MSU, White Sea Branch. 250 records from A review of the Australian endemic clam shrimp, Paralimnadia Sars 1896 (Crustacea: Branchiopoda: Spinicaudata). 3396 records from Red-throated diver national surveys in Scotland - raw data. 260424 records from Vascular plant specimens of Toyama Science Museum. 4 records from Hypselobarbus bicolor, a new species of large barb (Teleostei: Cyprinidae) from the Western Ghats of India. 20240 records from TPWD HARC Texas Coastal Fisheries Sabine Lake Bag Seine. 12788 records from Censos de aves del parque nacional Laguna Blanca. 3229 records from BID-AF2015-0004-NAC COLLECTION D'INSECTES DU LABORATOIRE D'ENTOMOLOGIE APPLIQUEE - FACULTE DES SCIENCES-UNIVERSITE DE LOME-TOGO. 1240 records from Report on the Danish Oceanographical expeditions 1908-1910 to the Mediterranean and adjacent seas - PelagicPolychaetes. 228377 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 5160 records from (Figure 4) Distribution and relative abundances of the benthic foraminifers recovered from the Jurassic section of DSDP Hole 79-547B. 2 records from Discovery of the spider wasp genus Sphictostethus Kohl, 1884 (Hymenoptera: Pompilidae: Pepsinae) in New Guinea, with description of two new species. 1686 records from (Supplementary data 1) Count data of the observed dinoflagellate cyst species from sediment core GeoB10709-5. 135163 records from SysTax - Herbaria. 946 records from Collection Mammalogie - ZSRO. 222 records from Type catalogue of Terebridae (Mollusca, Gastropoda, Conoidea) in the Natural History Museum, London, U. K.. 12 records from Two new species of Comesomatidae (Nematoda) from the East China Sea. 119434 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Trawl. 196 records from Eight new species of Dolichopodinae (Diptera: Dolichopodidae) from northern Iran. 11720 records from Loopkevers Grensmaas - Ground beetles near the river Meuse in Flanders, Belgium. 843 records from Inventarios de flora y fauna en bosques de niebla del municipio de Chámeza, Casanare. 64 records from Páramo de Belmira as an important centre of endemism in the northern Colombian Andes: new evidence from Pronophilina butterflies (Lepidoptera: Nymphalidae, Satyrinae, Satyrini). 301 records from Colección de Mamíferos - Universidad del Quindío. 1221 records from Systematics, biogeography and host-plant relationships of the Neotropical jumping plant-louse genus Russelliana (Hemiptera: Psylloidea). 4726 records from Avifauna en un área perturbada del bosque andino en el Parque Nacional Natural Farallones de Cali, corregimiento de Pance, Valle del Cauca (Colombia). 2030 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Macuira. 48 records from MVZ Herp Observations (Arctos). 136 records from New species and new records of predaceous midges in the genera, Schizonyxhelea Clastrier and Stilobezzia Kieffer from Mexico (Diptera: Ceratopogonidae). 1706 records from Sistemática de Bufo occidentalis Camerano 1879 (Anura: Bufonidae) en México. 48 records from Four new species of Paranaitis Southern, 1914 (Phyllodocidae, Annelida) from southern and southeastern Brazil. 36520 records from Fundación Miguel Lillo - Colección Criptogámica. 5 records from Description of two smallest field crickets from South America, Laureopsis nauta Jaiswara gen. nov., sp. nov. and Perugryllus estiron Jaiswara gen. nov., sp. nov. (Orthoptera, Grylloidea, Gryllidae, Gryllinae). 2 records from COL / ZPS "vallée de la Meuse". 7070 records from Savanna herbaceous vegetation, Lake Mburo National Park, Uganda. 52 records from A new species of Soikiella Nowicki (Hymenoptera: Trichogrammatidae) from Italy. 88 records from New species and records of Batraxis Reitter (Coleoptera: Staphylinidae: Pselaphinae) in continental China. 318 records from Benthic foraminifera groups of ODP Site 162-982. 4 records from A new morphologically cryptic species of Phyllomedusa (Anura: Phyllomedusidae) from Amazonian forests of northern Peru revealed by DNA sequences. 21 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 75 records from Brown algae specimens of Komatsu City Museum. 14693 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Bryophytes. 947 records from Collection Pisces - KAUMM. 622 records from Overview of the Ferdina - like Goniasteridae (Echinodermata: Asteroidea) including a new subfamily, three new genera and fourteen new species. 12 records from Données naturalistes de Noé Conservation. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 2 records from DREAL Auvergne - Arachnides - 2015. 14 records from On the taxonomy of the Italian endemic Hoplia dubia (Rossi, 1792), with the description of two new species (Coleoptera: Scarabaeidae: Melolonthinae). 3 records from New species of Lathrolestes Förster (Hymenoptera: Ichneumonidae) from Côte d’Ivoire. 22536 records from BCCM/IHEM biomedical fungi & yeasts. 12 records from Taxonomic notes and distribution extension of Durga Das’s leaf-nosed bat Hipposideros durgadasi Khajuria, 1970 (Chiroptera: Hipposideridae) from south India. 17739 records from Données CardObs (hors programme spécifique). 43 records from bmhs_beetle_collection. 4 records from A revision of the genus Boroecia Poulsen 1973 (Ostracoda, Halocypridae) with the descriptions of three new species. 72 records from Taxonomic notes on Palearctic Podalonia Fernald, 1927 (Hymenoptera, Sphecidae), with descriptions of four new species. 1830 records from Spatial distribution of a threatened multi-use species Afzelia africana Sm & Pers in Benin (West- Africa). 148701 records from Sustainable Rivers Audit. 8 records from A new species of Suphisellus Crotch from Mexico (Coleoptera: Noteridae). 12762 records from Natural Resources Wales (NRW) Licence Return Dataset. 14 records from Redescriptions and lectotype designations for two neotropical Elminae (Coleoptera: Elmidae). 2 records from Nomenclatural changes in Ochlerini (Hemiptera: Heteroptera: Pentatomidae: Discocephalinae). 616 records from Censo aéreo de poblaciones de borrego cimarrón (Ovis canadensis cremnobates) en Baja California, México. 12634 records from UWYMV Mammal Collection (Arctos). 3522 records from Centro de Recuperación de Fauna Silvestre "La Tahonilla". Cabildo de Tenerife. 13009 records from Données issues de la base de données SiRF et rattachées au groupe taxonomique "Orthoptères". 75750 records from Tamborine Mountain Weekly Bird Observations. 62 records from A new species of subgenus Homoneura from Northern China, with information of 12 species newly recorded (Diptera: Lauxaniidae: Homoneura). 19086 records from Wader survey on Uist in 2007. 641588 records from Data collected on scitizen science web portal www.ornitho.cat. 1779 records from Leicestershire Gastropod Records. 2544 records from Benthic diatom communities in pristine lakes and tarns, South Island. 81 records from A review of North American Elonus species, with description of E. gruberi n. sp. (Coleoptera: Tenebrionoidea: Aderidae). 282 records from Review of selected species of Campsurus Eaton 1868 (Ephemeroptera: Polymitarcyidae), with description of eleven new species and a key to male imagos of the genus. 22428 records from Pautas para el manejo y ordenamiento de una pesquería multiespecífica de crustáceos en un área natural protegida: El caso de la Ría Celestún, Yucatán. 5390 records from Diversidad taxonómica de las larvas de peces de Bahía Magdalena y zona nerítica adyacente (área prioritaria costera No. 4). 8 records from The Genus Criodion (Audinet-Serville, 1833) (Coleoptera, Cerambycidae): First Record for Panama. 13195 records from Colección de referencia de otolitos, Instituto de Ciencias del Mar-CSIC. 6 records from New species of Lonchaeidae (Diptera) from Switzerland and Serbia with arevised checklist of the Swiss fauna. 8 records from Description of Stegelletina lingulata sp. n. (Nematoda, Rhabditida, Cephalobidae) from xeric environments in Iran. 6698 records from Satellite tracking of female olive ridley sea turtles (Lepidochelys olivacea) nesting in the Wessel Islands, Northern Territory, 2005. 1 records from LEXEY RESHCHIKOV & ILARI EERIKKI SÄÄKSJÄRVI (2015) Seven new species of the genus Physotarsus Townes 1966 (Hymenoptera, Ichneumonidae) from South America. Zootaxa, 3972 (1): 026 - 042.. 36 records from Two new species of Medeventor Wheeler from South America (Diptera, Chloropidae, Oscinellinae). 2202 records from Colección de referencia del Herbario CUVC de la Universidad del Valle. 19 records from Données naturalistes opportunistes. 558 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Trochilidae. 185532 records from UAIC Ichthyological Collection. 422 records from Pollen analysis of sediment profile BLA0 from Blankensee. 18 records from A new species of Brachycephalus (Anura, Brachycephalidae) from the coast of Santa Catarina State, southern Atlantic Forest, Brazil. 20 records from A new genus of Tetracampidae (Hymenoptera) from South Africa. 1274 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales de Bahía Málaga, municipio de Buenaventura, Valle del Cauca. 210 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 1120 records from Données naturalistes d'Anthony DORE. 1156 records from Arachnid specimens of Ryukyu University Museum (Fujukan). 200 records from Antractic whale observation on a platform of opportunity abroad krill fishing vessel "Dalmor II", April - July 2011.. 4306 records from Records of the Western Australian Mycology Culture Collection. 6200 records from “Phytoplankton and Zooplankton data collected during the Black Sea cruises of UkrSCES R/V "Georgyi Ushakov" in 1992”. 23226 records from WDC Shorewatch Sightings. 79 records from The genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae: Syllinae) from Australia (second part): four new species and re-description of twelve previously described species. 850 records from Collection de C.C.H. Jongkind aux Monts Nimba. 435183 records from MVZ Bird Collection (Arctos). 16 records from Leaf insects from Luzon, Philippines, with descriptions of four new species, the new genus Pseudomicrophyllium, and redescription of Phyllium (Phyllium) geryon Gray, 1843, (Phasmida: Phylliidae). 6 records from Barsine amaculata, a new species from Vietnam (Lepidoptera, Erebidae, Arctiinae). 12 records from A new species of Stasimopus from the Eastern Cape Province of South Africa (Araneae, Mygalomorphae, Ctenizidae), with notes on its natural history. 6 records from Presence of the Glossosomatidae in Madagascar, with description of two species (Trichoptera). 99 records from Diversity and distribution patterns of Calcareous sponges (subclass Calcinea) from Martinique. 28 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 33 records from A new Pardosa species from northern Iran (Araneae, Lycosidae). 2184 records from Checklist of Serengeti Ecosystem Grasses. 2319 records from Pollen analysis of sediment core FEL2, Felchowsee, Germany. 4 records from Studies on the ant fauna of Melanesia V. The tribe Odontomachini.. 4 records from ZUEC-POP - Coleção de Polyplacophora do Museu de Zoologia da UNICAMP. 260259 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 135 records from Globigerinita spp. in sediment core MSM05/5_712-2. 94 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 77016 records from sarce_rockyshores. 32136 records from Digitization of plant specimens from Rhoen and Vogelsberg (FULD). 4 records from Two new troglobiotic palpigrades (Palpigradi: Eukoeneniidae) from Brazil. 2 records from New feather mites of the genus Amerodectes Valim and Hernandes (Acariformes: Proctophyllodidae) from passerines (Aves: Passeriformes) in Georgia, USA. 244 records from Species-richness in Neotropical Sericothripinae (Thysanoptera: Thripidae). 2 records from Studies of Peruvian Ptiliidae (Coleoptera) 5: Chaska nawi, a new genus and species of Acrotrichinae, Acrotrichini. 2 records from Rhinobatos manai sp. nov., a new species of guitarfish (Rhinopristiformes: Rhinobatidae) from New Ireland, Papua New Guinea. 62 records from A review of the genus Garra Hamilton 1822 of Bhutan, including the descriptions of two new species and three additional records (Cypriniformes: Cyprinidae). 15 records from Trichoptera of Serra da Jibóia, Bahia, Brazil: new species of Helicopsyche (Helicopsychidae) and new records. 43927 records from North Merseyside Local Species Data (DEFRA Grant 23169). 4 records from Perigomphus basicornis sp. nov. (Odonata: Gomphidae) from Anchicayá, Colombia. 15126 records from Tracheophyta collection of Biodiversity Center of Japan, Ministry of the Environment. 1252 records from SNH site condition monitoring of SSSIs for water beetles 2010. 57 records from Some Hydroids (Cnidaria, Hydrozoa) from the Great Australian Bight in the collection of the South Australian Museum. 12 records from Sycidiphaga, a new genus of Sycophaginae Walker, 1975 (Hymenoptera, Chalcidoidea, Agaonidae) associated with Ficus subgenus Sycidium in southern China. 12 records from Paracrossidius radekcervenkai (Coleoptera: Scarabaeidae: Aphodiinae), a new species from China. 516 records from Stem volume and biomass development in Lama Forest reserve, South Benin. Data published in the framework of JRS Benin project. 3 records from Eudorylaimus kahaqensis sp. n. (Nematoda: Dorylaimida: Qudsianematidae), an interesting new species from Iran. 6 records from The identity of Amplaria nazinta (Chamberlin, 1910): a century-old millipede mystery resolved (Diplopoda, Chordeumatida, Striariidae). 4446 records from Données de Lépidoptères de Bruno DAUGET - Dépt de l'ALLIER (03). 134406 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 8006 records from Knerer collection / Gschwendtner property. 236 records from Protozoa collection of National Museum of Nature and Science. 6 records from A new extinct species of Ataenius Harold from Baltic amber (Coleoptera: Scarabaeidae: Aphodiinae). 1098 records from Poissons et Crustacés d'eau douce de Polynésie Française. 3255 records from Registros Primates Neotropicales Convocatoria APC. 188 records from Taxonomy of the subgenus Pseudocypus Mulsant & Rey (Coleoptera: Staphylinidae: Staphylinini) and eight new species from China. 1076 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 2 records from Chaetanaphothrips kiyosumianus (Thysanoptera, Thripidae) new to India with first record of the male. 12 records from Exogoninae (Annelida: Syllidae) from Chilean Patagonia. 12 records from A new species of Deltaspis Audinet-Serville (Coleoptera: Cerambycidae: Cerambycinae) from Mexico. 5734 records from Ampliación de la base de datos de la ictiofauna insular del Golfo de California. 13724 records from Hormigas del Museo de Entomología de la Universidad del Valle. 5 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Pipridae. 792 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Picidae. 14 records from Morphological redescription of Culex (Microculex) davisi and Cx. (Mcx.) imitator (Diptera: Culicidae) including structures and stages not previously described. 255 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Recurvirostridae. 12 records from Two new species of Haploperla (Plecoptera: Chloroperlidae) from China. 3435 records from Benthos Chirnov Basin 1986 and 2002. 708 records from Sponges of the Guyana Shelf. 567 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 10101 records from Base de datos del Municipio General Heliodoro Castillo, Guerrero (120. Sierra Madre del Sur). 236 records from Revision of world Ooderella Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae), with description of the first males for the genus. 18684 records from Vleermuiskasten.nl - Bats in bat boxes in The Netherlands and Belgium. 8 records from Arcturina serrulatus sp. nov. and a new record of Limnoria rhombipunctata (Crustacea: Malacostraca: Isopoda) from South Korea. 1 records from The extinct river shark Glyphis pagoda from the Miocene of Myanmar and a review of the fossil record of the genus Glyphis (Carcharhiniformes: Carcharhinidae). 25 records from Reef Life Survey. 172 records from (Table 3) Abundances of planktonic and benthic foraminifera in ODP Hole 130-807C. 3416 records from Florística de las cactáceas de Durango. 225 records from Data from ILAM surveys conducted by ARCOS in Mukura landscape for year 2016. 3 records from Redescription of two species of Asterocheres Boeck, 1860 (Copepoda: Siphonostomatoida), A. corneliae Schirl, 1973 and A. boeckii (Brady, 1880), and proposal of a new genus for Asterocheres fastigatus Kim, 2010. 279 records from New and little known bees of the genus Sphecodes Latreille, 1804 (Hymenoptera: Apoidea: Halictidae) from Central Asia. 8 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Abbey Craig SSSI. 20414 records from Auckland Museum NZ Marine Collection. 3 records from (Table 5) Organic matter contents and paleoproductivities at DSDP Site 75-532. 100 records from First report of Cheiloneurus exitiosus (Perkins, 1906) and Helegonatopus dimorphus (Hoffer, 1954) (Hymenoptera: Encyrtidae) from Japan, with remarks on their abundance in rice paddies. 62 records from Données de Mammifères marins en Polynésie française issues du South Pacific Whale Research Consortium. 2 records from Arthropoden aus südostalpinen Höhlen.. 102 records from A new species of snail-case caddisflies (Trichoptera: Helicopsychidae) and new records of caddisflies from Chapada Diamantina, Bahia, Brazil. 6 records from Trichomycterus santanderensis: A new species of troglomorphic catfish (Siluriformes, Trichomycteridae) from Colombia.. 14 records from Microcambeva ribeirae sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new sarcoglanidine catfish from the Rio Ribeira do Iguape basin, southeastern Brazil.. 30 records from Rare myodocopid ostracods from Mesozoic sections of Hungary: summary, revision and description of new taxa. 21502 records from VERTEBRADOS DE VALOR ESPECIAL EN ÁREAS PROTEGIDAS DE LA ARGENTINA. 18 records from First record of Tettigettalna mariae Quartau & Boulard, 1995 (Insecta: Hemiptera: Cicadoidea) in Spain. 168834 records from Invertebrate Common Standards Monitoring and ISIS Test Data. 3 records from Taxonomic notes on the genera Brypoctia Schoorl, 1990 and Schreiteriana Fletcher & Nye, 1982 (Lepidoptera, Cossidae). 17512 records from Espèces envahissantes et menacées des pâturages naturels de la zone soudano-guinéenne, données mobilisées dans le cadre du projet BID. 4 records from A new species of Prosopistoma Latreille, 1833 (Ephemeroptera: Prosopistomatidae) from South India. 19968 records from Palaeontologische Sammlung der Freien Universitaet Berlin. 49040 records from National Dormouse Database (NDD). 3637 records from Lepidoptera collection of NW Europe. 1494 records from Inventory Pobè forest in South East of Benin. 4 records from Description of a new species of Cytaea Keyserling 1882 from Fiji (Araneae: Salticidae). 54 records from Variación genética del manatí (Trichechus manatus), en el sureste de México y monitoreo con radio-transmisores en Quintana Roo. 126170 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 57 records from A review of the genus Scaponopselaphus Scheerpeltz (Insecta: Coleoptera: Staphylinidae). 20 records from Two new species of cave crickets Endecous (Notoendecous) Gorochov, 2014 (Orthoptera: Grylloidea: Phalangopsidae) from northeastern Brazil. 39 records from European species of the Gnaphosa alpica complex (Araneae, Gnaphosidae). 10785 records from Vascular plants in Danish coastal meadows. 263 records from (Table 2) Relative abundance of coccoliths at DSDP Hole 75-530A. 101831 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 314 records from Tejidos colectados en la ventana de biodiversidad del Complejo Cenagoso de Zapatosa, Municipio de Chimichagua, Cesar, Colombia.. 2 records from Myolaimus ibericus sp. n. (Nematoda, Rhabditida, Myolaimidae) from southern Iberian Peninsula, with a key to species of the genus. 1798 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 94-610A. 4 records from A new genus and species of Atalophlebiinae (Insecta: Ephemeroptera: Leptophlebiidae) from Palni hills of the southern Western Ghats, India. 10 records from Aretidris, a new genus of ants (Hymenoptera: Formicidae: Myrmicinae) from the mountains of Luzon Island, Philippines. 182 records from (Table A) Wet weight night biomass of dominant mesozooplankton groups obtained from night catches within the Bismark Polygon in June 2001 and June-August 2002. 6528 records from (Figure 11) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-538A. 48 records from Inventario de Murciélagos Floreña I, Yopal, Casanare. 20381 records from Collembola collection of Arne Fjellberg, Norway. 92 records from Nematoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 186 records from Revision of the Hybobathus arx and Pelecinobaccha summa species groups (Diptera: Syrphidae). 11409 records from V. N. Karazin Kharkiv National University herbarium. 10 records from A new species of genus Parhyale Stebbing, 1897 (Crustacea, Amphipoda, Hyalidae) from Gujarat State, India. 88 records from Satanoperca curupira, a new cichlid species from the rio Madeira basin in Brazil (Teleostei: Cichlidae). 7278 records from Computarización de la colección de mamíferos del Centro de Educación Ambiental e Investigación Sierra de Huautla (CEAMISH) de la Universidad Autónoma del Estado de Morelos (UAEM). 540 records from Monitoreo biológico en la cuenca RUT, campaña ARA - RARE - CVC – Asociación Calidris. 162 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 19368 records from Fish collection, Natural History Museum, University of Oslo. 30 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 33012 records from Database for alien invasive plants occurrences in Germany. 7106 records from Marine Invertebrate from Argentina, Uruguay and Chile. 20 records from Some taxonomic notes on the Caradrina (Eremodrina) filipjevi (Boursin, 1936) species group (Lepidoptera, Noctuidae). 54423 records from Insectes Lépidoptères Rhopalocères de France métropolitaine. 20781 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 466 records from Database on reference specimens for medicinal plants of the Meliaceae family, conserved at the CNARP herbarium. 540 records from Plantas de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 11817 records from Census of plant species in Pahou forest reserve. 3003 records from LACM Invertebrate Paleontology. 10 records from Zebraodes, new genus, with a new species from Vietnam (Lepidoptera: Tortricidae: Tortricinae: Archipini). 327 records from Artsrike vegkanter i Haugesund. 12 records from Rhigonema naylae n. sp. (Rhigonematomorpha: Rhigonematidae) a new parasitic nematode from a Japanese polydesmid millipede (Polydesmida: Xystodesmidae). 12 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 169644 records from ATBI Parc national du Mercantour / Parco naturale Alpi Marittime. 156 records from Red list project inventory, fungi. 4 records from New species of the earthworm genus Zapatadrilus (Clitellata, Acanthodrilidae) from northern Mexico. 16 records from A new species of lizard of the L. wiegmannii group (Iguania: Liolaemidae) from the Uruguayan Savanna. 28707214 records from Anillamiento SEO_Bird ringing. 2 records from Contributions a la faune Myriapodologiwue Mediterraneenne. 739233 records from Vascular plant field notes, NTNU University Museum. 60 records from Description of three new species of Crenitis Bedel from China, with additional faunistic records for the genus (Coleoptera: Hydrophilidae: Chaetarthriinae). 92 records from The majestic canopy-emergent genus Dinizia (Leguminosae: Caesalpinioideae), including a new species endemic to the Brazilian state of Espírito Santo. 2 records from A new mesoserphid wasp from the Middle Jurassic of northeastern China (Hymenoptera, Proctotrupoidea). 66564 records from Données SAPROX - Benoît Dodelin (mars 2014). 146 records from Chenopodium & Dysphania. 502 records from ZUEC-APL - Coleção de Aplacophora do Museu de Zoologia da UNICAMP. 121 records from (Table T1) Kerogen and organic constituents in ODP Hole 183-1138A, Kerguelen Plateau. 9370 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2006. 50 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2006. 27987 records from Centre de Ressources Biologiques de l'Institut Pasteur. 4516 records from Wildwatch North Pennines AONB project records for Cumbria. 2610 records from (Table 2) Pleistocene nannofossil range chart for ODP Hole 134-828A. 8318 records from DBG Mirabilis rotundifolia Demographic Monitoring. 15 records from Checklist and new species of caddisfly (Insecta: Trichoptera) from Roraima state, Brazil. 2 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 1 records from Biodiversity and Biogeography of Chthamalid Barnacles from the North-Eastern Pacific (Crustacea Cirripedia). 11840 records from Alterra (NL) - Microarthropods inventories by Henk Siepel on various locations. 36 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 12 records from Taxonomic notes on Hydroidomedusae (Cnidaria) from South China Sea I: Family Eucodoniidae (Anthomedusae). 86 records from Inventarios de Murciélagos de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 6591 records from Museo Laboratorio de Entomología (MENT-UT). 18 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cariamidae. 74 records from Comunidad de Macroinvertebrados de un Área Degradada por Actividad Minera en la Costa Caucana. 15420 records from The Coleoptera collection (EC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 932 records from Colección Mastozoológica Universidad de los Llanos. 120 records from Catálogo de maíces nativos generada en la tesis El sistema milpa y sus recursos fitogenéticos en Santa María Tlahuitoltepec, Oaxaca. 9986 records from Planktonic foraminifera in ODP Hole 160-963A. 4 records from Anaxiphomorpha hexagona sp. n., a new, unusual swordtail cricket collected from Motuo County, Xizang, China (Orthoptera: Grylloidea: Trigonidiidae: Trigonidiinae). 10 records from Description of female of Titidius urucu Esmerio & Lise, 1996 (Araneae: Thomisidae). 28539 records from Records of Invasive Non Native Species held on the Cofnod database. 2 records from Deux especes nouvelles pour la science du genre Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). - Two new species for the science in the genus Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). 65362 records from Ground Beetle of Japan Specimen Database. 42 records from Clubionidae from Laos and Thailand (Arachnida: Araneae). 45 records from Ants on Kiritimati Island Atoll in March 2013. 19094 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 26 records from Two new species and a new record of the fungivorous genus Terthrothrips from China (Thysanoptera: Phlaeothripidae). 50 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 12 records from The uncommon Neotropical genus Pazius Navás, 1913 (Mecoptera: Bittacidae): a comprehensive synthesis, with description of a new Brazilian species. 5471 records from Collection entomologique de l'Université Laval (ULQC). 18918 records from BioGIS - Vascular plants - SPNI. 1750 records from Living coccolithophores from the Gulf of Sirte during the summer of 2008. 295322 records from National Trust for Scotland Species Records. 358 records from Seven new species of the Neotropical electric fish Gymnotus (Teleostei, Gymnotiformes) with a redescription of G. carapo (Linnaeus).. 1163 records from Oceanexploration2002_vers4. 88 records from The new spider genus Palindroma, featuring a novel synapomorphy for the Zodariidae (Araneae). 40860 records from Distribution de quelques espèces de plantes agroforestières et médicinales au Bénin. 251 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 14 records from A second species of Smetanabatrus (Coleoptera: Staphylinidae: Pselaphinae). 16 records from Ansienulina, a new genus of jumping spiders from tropical Africa (Araneae: Salticidae: Thiratoscirtinae). 34 records from Sponge epizoism in the Caribbean and the discovery of new Plakortis and Haliclona species, and polymorphism of Xestospongia deweerdtae (Porifera). 14241 records from (Table T3) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1138A. 682 records from St Andrews BioBlitz 2015. 278 records from Revision of the myrmicine ants of the Adelomyrmex genus-group (Hymenoptera: Formicidae).. 114 records from Observations d'espèces animales exotiques envahissantes en Auvergne. 1098 records from (Table 7) Species composition of clusters, ODP Holes 139-856A and 139-857A. 13 records from Two new species of Adapterops (Coleoptera: Anthribidae) from protected areas of northern Madagascar, with a key to species, and new faunistic data on the genus. 6 records from A new small bent-toed gecko of the genus Cyrtodactylus (Squamata: Gekkonidae) from the lower slopes of Mount Tambora, Sumbawa Island, Indonesia. 1443 records from Artskartlegging flomsikringstiltak, Kvam 2013. 14 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 2 records from New species of Leleja (Orthoptera: Gryllinae; Gryllini) with first female description for the genus. 52 records from Colección de Referencia de Mamíferos del Museo de Ciencias de la Universidad El Bosque. 752 records from Levantamento do estrato arbustivo da vegetação de campina do RDS Uatumã. 70 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 2 records from Revision of Hindumanes Logunov, 2004 (Araneae: Salticidae: Lyssomaninae), with description of a new species from the Western Ghats of Kerala, India. 10 records from Rediscovery and redescription of Centrodora damoni (Girault) (Hymenoptera: Aphelinidae) from Australia, an egg parasitoid of Gonipterus spp (Coleoptera: Curculionidae), after nearly a century. 96 records from On the taxonomy of Korean jumping plant-lice (Hemiptera: Psylloidea). 124 records from Diversity of marine bryozoans inhabiting demosponges in northeastern Brazil. 36228 records from Donnée naturalistes d'Aurélien HUGUET. 15 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 201 records from Three new species of Parapercis (Perciformes: Pinguipedidae) and first records of P. muronis (Tanaka, 1918) and P. rubromaculata Ho, Chang & Shao, 2012 from Australia. 21144 records from EAN - Herbário Jaime Coelho de Moraes. 58 records from Thirteen new records of ferns from Brazil. 450 records from Collection des données de biodiversité marine de Polynésie française - IRD Nouvelle-Calédonie. 162 records from Aves del Santuario de Fauna y Flora Malpelo entre 2006 y 2013. 40 records from Seawater carbonate chemistry and biological processes of Amphisorus hemprichii, Amphisorus kudakajimensis and Calcarina gaudichaudii during experiments, 2011. 291 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 220 records from (Table S1a) Measured tomographic parameters for Oridorsalis umbonatus during the PETM for ODP Site 208-1263. 6 records from New species and records of Scaphobaeocera CSIKI from New Guinea (Coleoptera: Staphylinidae: Scaphidiinae). 12 records from Two new and one redescribed species of Acanthobothrium (Cestoda: Onchoproteocephalidea: Onchobothriidae) from Dasyatis akajei (Myliobatiformes: Dasyatidae) in the China Sea. 706 records from Contribución a la distribución, ecología y estado de conservación de dos especies del género Sceloporus, endémicas de la región del Cabo, Baja California Sur. 45856 records from BHCB-SL - Herbário UFMG - Samambaias e Licófitas. 12288 records from The Pisces Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 61718 records from Données "faune" hors insectes pour le SINP île de France. 10 records from Revision of the shore-fly genus Peltopsilopa Hendel (Diptera: Ephydridae). 15078 records from Samoa Biodiversity Database. 585 records from (Table 2) Relative abundance of selceted benthic foraminifera taxa of DSDP Hole 93-605. 10 records from The Pselaphinae (Coleoptera: Staphylinidae) of Madagascar. VI. Description of Ambohitantella banari gen. et sp. n. with notes on Nearticerodes Jeannel, 1954 and Triceratomerus Jeannel, 1960. 1780 records from Herbier Boreal Confluence (BOUM). 20 records from On some minuscule spiders (Araneae: Theridiosomatidae, Symphytognathidae) from the Chocó region of Ecuador with the description of ten new species. 86 records from Revision of the Agrilus gratiosus species-group (Coleoptera, Buprestidae, Agrilinae). 741 records from (Table T3) Calcareous nannofossil abundance of ODP Hole 189-1171A sediments. 875 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Sandwood Estate during 1998 â 2006.. 1026 records from Kieppi bird collection. 27649 records from Arthropod collection, Tromsø Museum. 1860 records from Données naturalistes de Hervé BOUYON. 111632 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 321 records from Vegetación de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 86 records from Review of the species of the Cirolana ‘ parva - group’ (Cirolanidae: Isopoda: Crustacea) in Indonesian and Singaporean waters. 4 records from The type specimen and generic placement of Tridactylus galla Saussure, 1895 (Orthoptera: Caelifera: Tridactylidae). 21 records from First records of Glaresidae (Coleoptera) in China, with the description of a new species from Inner Mongolia and Shaanxi. 23372 records from Escarabajos coprófagos (Coleoptera: Scarabaeidae: Scarabaeinae) de bosques secos Colombianos de la Colección Entomológica del Instituto Alexander von Humboldt. 1366 records from Lama Forest reserve Inventory, South Benin. Data published in the framework of JRS Benin project. 8 records from Description of four new species of the Cirolana ‘ parva group’ (Crustacea: Isopoda: Cirolanidae) from Thailand, with supporting molecular (COI) data. 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1435 records from (Table 3) Distribution of benthic foraminifers from ODP Hole 134-828A. 96 records from Nanofaunaartenliste. 12809 records from Macroinvertebrate abundance in river biotopes across England and Wales. 17252 records from DREAL_PACA_-_N2000_-_SMIGIBA_2017_12_18. 461506 records from UF FLMNH Ichthyology. 64027 records from UAM Insect Observations (Arctos). 36188 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 698 records from Inventario Nacional de Candelilla (Euphorbia antisyphilitica) Fase I.. 6964 records from GRT gaz inventaire PNRL. 337 records from Caracterización de coberturas vegetales en el páramo de Santurbán. 5 records from A spectacular new species of seadragon (Syngnathidae). 334 records from (Fig. 5) Distribution of Chironomids of sediment core Lz1103 from Duck Lake. 32236 records from Invertebrata Collection of Institute of Systematics and Evolution of Animals. 121 records from Copepod order counts from various box corer samples of cold-water coral substrates in the Porcupine seabight. 8 records from Two new species of Hyalella (Crustacea, Amphipoda, Hyalellidae) from state of Rio Grande do Sul, Southern Brazil. 800 records from 20th century Betula pubescens ssp. czerepanovii tree- and forest lines in Norway. 39 records from Solomon Islands Ants 2015. 46655 records from Herbarium Erlangense. 160 records from Echinoderms occurence in a strongly contaminated Bay (Portman, Spain), using ROV and Scuba-diving surveys. 1002 records from Herbario HUAZ Enrique Forero. 6 records from New synonym of Tipula (Vestiplex) wahlgrenana Alexander, 1968 (Diptera: Tipulidae). 156 records from Upper Tapanahony Expedition 1991. 36 records from Hemiptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 40 records from Seawater carbonate chemistry and boron incorporation of planktic foraminifer Orbulina universa during experiments, 2011. 46 records from Caracterización de la ictiofauna de la ciénaga Honda, Tanguí. 2904 records from TTRS Mammals. 82 records from Review of Ptilomera (Ptilomera) (Hemiptera: Heteroptera: Gerridae) from India, with description of a new species. 10317 records from Vascular plant specimens of Aomori City Forestry Museum. 7845 records from Enquête préliminaire Coléoptères saproxylophages de France. 14 records from Description of Paraceto gen. n. and a relimitation of the genus Cetonana (Araneae: Trachelidae). 121929 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 31035 records from Moss herbarium, UiB. 110 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Myriapoda National Collection (MACNMy). 61366 records from Derek Lott Coleoptera Dataset. 95364 records from Observatoire de la Biodiversité des Jardins (OBJ). 338 records from A contribution to the knowledge of the subfamily Panagaeinae Hope, 1838 from Africa. Part 2. Revision of the Craspedophorus leprieuri and C. regalis groups (Coleoptera: Carabidae). 842 records from Monitoreo biológico en la cuenca La Paila, campaña ARA - RARE - CVC – Asociación Calidris. 93 records from Menieroclerus gen. nov.: A new genus for Thanasimodes nigropiceus (Kuwert, 1893) (Coleoptera: Cleridae: Clerinae). 4044 records from Patrones biogeográficos de las cactáceas columnares de México. 4 records from A new species of Eupariini from Eocene Baltic amber (Coleoptera: Scarabaeidae: Aphodiinae). 10 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 70 records from Bacteria from Penguin Guano, Antarctica. 14 records from Populations ensauvagées de Lapin de garenne en Nouvelle-Calédonie issues du CEN-NC et de l'IRD-NC. 2012. 4754 records from Dutch Mammal Society (NL) - Mouse observations of life trap studies extracted from historic reports. 1160 records from The symphytognathoid spiders of the Gaoligongshan, Yunnan, China (Araneae: Araneoidea): Systematics and diversity of micro-orbweavers. 15267 records from Herbario de Plantas Vasculares de la Asociación BIGA para el estudio del patrimonio natural de Galicia: FBIGA. 32 records from New and little-known species of the genus Lacon Laporte, 1838 (Coleoptera: Elateridae) of Afghanistan and adjacent countries. 1588 records from Isle of Wight non-native invasive species. 20 records from Beitrag zur Kenntnis der Oribatiden Mitteleuropas (Neue Liacarus-Arten). 78 records from A review of the Malagasy Pachypanchax (Teleostei: Cyprinodontiformes, Aplocheilidae), with descriptions of four new species.. 6994 records from Aves acuáticas y marinas en las costas de Colima, Guerrero y Oaxaca. 18900 records from Arctic Species Trend Index (ASTI) : Freshwater. 17856 records from City of Amsterdam (NL) - Fyke Fishing Piet Ruiter. 22 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Rhidorroch Woods SSSI. 5103 records from Census of plant species in Monts-Kouffè regions, center Benin. 183 records from Succession of benthic hard-bottom communities abundance at Liliguapi, Paso Comau, Chile, in 2010. 456 records from Investigación y manejo para la conservación de tortugas amenazadas de los humedales llaneros. 4 records from A new species of Lobesia Guenée, 1845 from Thailand (Lepidoptera: Tortricidae: Oletheutinae). 12645 records from Mayflies (Ephemeroptera) of Ireland. 2728 records from Caracterización de la vegetación en los sectores de Aipe (Huila), Yaví (Tolima) y Dagua (Valle del Cauca), como insumo para la identificación de oportunidades de conservación y la recuperación de servicios ecosistémicos del bosque seco. 94 records from (Table IV) Abundance of isopoda families during RSS James Clark Ross cruise JR144. 2278 records from SWECO. 15 records from Taxonomic revision of Paraustrosimulium Wygodzinsky & Coscarón: reassignment of Austrosimulium colboi and description of P. obcidens n. sp. from Western Australia. 2992 records from Stoneworts in Wales. 27 records from Cylapofulvidius Chérot & Gorczyca, 2000 — a synonym of Fulvidius Poppius, 1909 (Hemiptera: Heteroptera: Miridae: Cylapinae). 2598 records from Fundación Miguel Lillo - Colección Fanerogámica. 4 records from On Sphallambyx mexicanum and key to species of Sphallambyx (Coleoptera, Cerambycidae, Cerambycinae). 2 records from A new species of Marsipococcus Cockerell & Bueker (Hemiptera: Coccomorpha: Coccidae) from Malaysia. 109 records from Reptile distribution along the River Bure, Broadland (2010). 399023 records from Herbarium of Taiwan Forestry Research Institute. 1 records from Alloionema californicum n. sp. (Nematoda: Alloionematidae): a new alloionematid from USA. 1162 records from Collection scientifique et pédagogique de l'Ecole Normale Supérieure de Lyon. 9105 records from HDJF - Herbário Dendrológico Jeanine Felfili. 124 records from Revision of early taxa of Australian gall midges (Diptera: Cecidomyiidae). 675 records from Tillegg Røtinga i Os. 50 records from New lineages of Lebinthini from Australia (Orthoptera: Gryllidae: Eneopterinae). 57 records from Revision of the Australian species of Agrotera Schrank (Lepidoptera: Pyraloidea: Crambidae: Spilomelinae). 286 records from An update on the spider genus Hexophthalma (Araneae: Sicariidae) in the Afrotropical region, with descriptions of new species. 354 records from Biological Recording in Scotland - Scotsman Wildlife Surveys. 34 records from New distribution records of the savanna specialist fungus-farming ant Cyatta Sosa-Calvo et al. (Hymenoptera: Formicidae: Myrmicinae). 982 records from Données naturalistes de Wilfried RATEL. 1302 records from Réseaux écologiques/Trame verte et bleue. 2076432 records from Welsh BSBI data (ex-VPDB dataset) at hectad resolution. 9579 records from Algae, Specimens, Agder naturmuseum (KMN). 1236 records from Crustacean specimens of Kaizuka City Museum of Natural History. 134 records from New leaf- and litter-dwelling species of the genus Pholcus from Southeast Asia (Araneae, Pholcidae). 368 records from Flora vascular de los manglares de Marismas Nacionales, estado de Nayarit. 8 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 619008 records from Oiseaux de France métropolitaine 2009-2013 en période hivernale. 902352 records from Instituto de Botánica Darwinion. 2013 records from BoGART. 8 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 7666 records from Guía ilustrada de los Staphylinidae (coleóptera) de México. 628 records from University of Amsterdam (NL) - Páramo Vegetation Research, Paramo "El Almorzadero", Colombia. 11651 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213. 6 records from Eidinemacheilus, a new generic name for Noemacheilus smithi Greenwood (Teleostei; Nemacheilidae). 5 records from The genus Vieira Navás (Neuroptera: Chrysopidae): a new species, a key to the species, and new geographic records. 9204 records from English Nature and NCC Oxfordshire Surveys. 90 records from Mammalia (NHCA-MM). 1203 records from Konsekvensutredning naturmangfold E6 Åsen - Mære. 5 records from Eulepida mbala, a new species from Zambia (Coleoptera: Scarabaeidae: Melolonthinae). 6 records from A new species and a key to species of the genus Coptotettix Bolivar, 1887 from India (Orthoptera: Tetrigoidea, Tetrigidae). 447 records from A revision of Bittacomorphinae with a review of the monophyly of extant subfamilies of Ptychopteridae (Diptera). 30928 records from Freshwater Diversity Identification for Europe (FREDIE) - funded by the German Leibniz association ( SAW-2011-ZFMK-3). 10 records from Données naturalistes d'Olivier DUFOUR. 10 records from Larval morphology of benthic and interstitial water mites (Acari: Hydrachnidia) from a Luxembourgian stream. 31646 records from Naturalis Biodiversity Center (NL) - Echinodermata. 40 records from Colección de Referencia de Poríferos del Museo de Ciencias de la Universidad El Bosque. 8 records from new endemic Synagapetus species (Trichoptera: Glossosomatidae) from Madeira Island (Portugal). 267332 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1011 records from Vegetación de los remanentes de bosque andino, municipio de San Francisco (Cundinamarca). 28 records from First description of the male of the spider Tibellus paraguensis Simon, 1897 (Araneae: Philodromidae), with new distribution records. 82135 records from Exotic plant occurrences in Wallonia. 195 records from (Table 2) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840A. 2 records from Nothrus bicolor. 1001616 records from Neptune Deep-Sea Microfossil Occurrence Database. 3972 records from Données Cetonidae -1981-2014-LACOSTE Frédéric. 86 records from Données naturalistes de Françoise SERRE-COLLET. 1180 records from Les mollusques terrestres de la faune de Corse : Mission 2017. Muséum national d'Histoire naturelle, Paris et DREAL Corse. 32 records from Revision of the horseface loaches (Cobitidae, Acantopsis), with descriptions of three new species from Southeast Asia. 14 records from Redescription of the Philippine leafhopper genus Iposcopus Baker (Hemiptera: Cicadellidae: Idiocerinae). 58 records from Two new species of Bebearia Hemming, 1960, as further evidence of centre of endemism of butterflies in Western Nigeria (Lepidoptera: Nymphalidae: Limenitinae). 42 records from The Oribatid Family Phthiracaridae III. Redescription of Phthiracarus nitens (Nicolet). 104948 records from Amphibians of the Former USSR. 50 records from Revision of African Apiocera (Diptera: Apioceridae). 4788 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 253 records from Données naturalistes d'Olivier LAURENT. 308382 records from SIO Marine Vertebrate Collection. 1288 records from English Nature Oxfordshire Fen Survey 1990-1991 (A Comparative Survey of Rich Calcareous Fens of Oxfordshire) (as held by Thames Valley Environmental Records Centre). 1562 records from (Table T17) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones P14-P18. 18 records from Two new genera of predatory katydids (Orthoptera: Tettigoniidae: Meconematinae) from the Amazon rainforest. 4 records from Phylloicus mirabilis (Trichoptera: Calamoceratidae), a new species from Rio de Janeiro state, southeastern Brazil. 4 records from A new species of Mud Snake (Serpentes, Homalopsidae, Gyiophis Murphy & Voris, 2014) from Myanmar with a first molecular phylogenetic assessment of the genus. 152046 records from CZE National PGR Inventory. 40581 records from CWS: Waterbird colony database (Atlantic region). 2 records from The assassin bug genera Nagustoides and Stenolemus (Hemiptera: Heteroptera: Reduviidae) newly recorded from Japan. 22 records from Six new species of Afrotropical Allodia (Diptera: Mycetophilidae): DNA barcodes indicate recent diversification with a single origin. 2 records from A new species of gall midge (Diptera: Cecidomyiidae) damaging ornamental Callistemon (Myrtaceae) in Australia. 645 records from (Table T12) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P14-P18. 527 records from Mammal specimens of Saitama Museum of Natural History. 89 records from ARTIFEX_2017_12_18. 2 records from Acrosternum heegeri Fieber, 1861 (Hemiptera: Heteroptera: Pentatomidae), another Mediterranean bug expanding to the north. 1666 records from Marine data from The Wildlife Trusts (TWT) Dive Team; Somerset, Cornwall and Sussex; 2014-2015. 641418 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 3036 records from Elasmobranquios mexicanos. 37227 records from Données naturalistes de Franck NOEL. 100 records from New species and new records of linyphiid spiders from the Indo-Malayan Region (Araneae, Linyphiidae). 11 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Diomedeidae. 12 records from Fungus-feeding thrips of the genus Stephanothrips in Australia (Thysanoptera, Phlaeothripinae). 266 records from Description of Haploblepharus kistnasamyi, a new catshark (Chondrichthyes: Scyliorhinidae) from South Africa.. 4028 records from ZUEC-ARA - Coleção de Aracnideos do Museu de Zoologia da UNICAMP. 12 records from Review of the fish genus Epinnula Poey (Perciformes: Gempylidae), with description of a new species from the Pacific Ocean. 48 records from New species and records of Corydalidae (Insecta: Megaloptera) from Myanmar. 6252 records from Florística de las gramíneas de Chihuahua. 4 records from A new species of Orybina Snellen, 1895 from India (Lepidoptera, Pyralidae, Pyralinae). 31068 records from Surveys of Octocoral communities, benthic cover and environmental factors on coral reefs of the Great Barrier Reef, Australia (1996 to present). 6 records from A new species of semi-terrestrial freshwater crab (Crustacea: Decapoda: Brachyura: Potamidae) from the Central Highlands of Vietnam. 153339 records from Atlas des Orthoptères et Mantides de France métropolitaine. 73289 records from SDSM Invertebrate Collections. 1114 records from Corn bunting breeding distribution in Scotland. 2 records from A new species of the genus Megophrys (Anura: Megophryidae) from Yunnan Province, China. 24 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 51 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña diciembre 2010. 48 records from Revision of the Diplommatinidae (Gastropoda: Cyclophoroidea) from Java. 340 records from Thistles and numbers of observed invertebrates, fungi and damage types. 4888 records from SPC PROCFish/C Fish Observations Tonga 2008. 13719 records from Base de datos de nombres técnicos o de uso común en el aprovechamiento de los agaves en México. 545 records from (Table 6) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-849B. 1416 records from Occurrences des observations de la campagne REMMOA Guyane (2008). 2 records from Conservación de la población de Loro Orejiamarillo (Ognorhynchus icterotis) en el piedemonte llanero, departamento del Meta. 222 records from Taxonomy and Biogeography without frontiers – WhatsApp, Facebook and smartphone digital photography let citizen scientists in more remote localities step out of the dark. 14 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 1434 records from Enquête DREAL Auvergne Ecrevisses. 3006 records from Peces de la cuenca alta y media del río Bita, Vichada (Colombia). 2 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Formicariidae. 20 records from New species and new records of Uropodina from Virginia, USA (Acari: Mesostigmata). 9254 records from Arctic Marine Fish Museum Specimens. 11 records from Nematomorpha from Hong Kong and description of a new species from Malaysia. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 56 records from Checklist of the freshwater snails (Mollusca: Gastropoda) of Mongolia. 1369785 records from Naturalis Biodiversity Center (NL) - Mollusca. 39 records from Two new species of the genus Nemognathomimus (Coleoptera: Cerambycidae) from Mexico and Guatemala. 12 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 115 records from Mamíferos de los Parques Ecológicos Distritales de Humedales de Bogotá, D.C.. 6 records from First record of Cephenniitae in the Bismarck Archipelago, Papua New Guinea, with description of new species of Cephennodes and Cephennomicrus of Mussau and Manus Islands (Coleoptera, Staphylinidae, Scydmaeninae). 85747 records from Green Plant Herbarium (TRT). 66 records from Bedfordshire Stylops (BNHS) - 1930-1971. 34802 records from The Hemiptera collection (EH) of the Muséum national d'Histoire naturelle (MNHN - Paris). 374 records from A taxonomic review of the genus Palumbina Rondani, 1876 (Lepidoptera, Gelechiidae, Thiotrichinae) from China, with descriptions of twelve new species. 220 records from Biodiversity and notes on carabid beetles from Angola with description of new taxa (Coleoptera: Carabidae). 156 records from Université Pédagogique Nationale de Kinshasa (UPN) - Données botaniques (2011)- Projet CABIN. 140 records from Porifera Collection - Instituto Nacional de Pesquisas da Amazônia. 18 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 8618 records from Données naturalistes de Ségolène FAUSTEN. 45 records from Observations of the emergence of Fijian cicadas in September 2017. 4200 records from (Table T4) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1050C. 14 records from A new species of the lizardfish genus Synodus (Aulopiformes: Synodontidae) from the western Pacific Ocean. 21 records from Three new species of the genus Caccothryptus Sharp, 1902 from Asia (Coleoptera: Limnichidae). 16 records from A new species and subgenus of Pachylaelaps Berlese from Turkey (Acari: Pachylaelapidae). 7 records from First record of the genus Graptopeltus Stål (Hemiptera: Heteroptera: Rhyparochromidae) from the Korean Peninsula, with description of a new species. 9717 records from Arthropods from Praia da Vitória (Terceira, Azores, Portugal). 12 records from Two new Chinese species of Tomocerus at different stages of troglomorphic adaptation (Collembola, Tomoceridae). 48 records from Two new emerald geometrid species of Telotheta Warren from Ecuador and Bolivia (Lepidoptera: Geometridae, Geometrinae, Lophochoristini). 904 records from Florida Museum Environmental Archaeology Baptizing Springs Zooarchaeological Data. 4647 records from Actualización de la Colección de Collembola de México y ácaros edáficos. Catálogo de oribátidos de México. 1170 records from Livingstone Museum Bat Collection. 86 records from Notes on the snake eels of the genera Apterichtus and Ichthyapus (Anguilliformes: Ophichthidae) of the Central and South Pacific, with the description of a new species.. 98 records from Acanthopagrus taiwanensis, a new sparid fish (Perciformes), with comparisons to Acanthopagrus berda (Forsskål, 1775) and other nominal species of Acanthopagrus.. 6830 records from Plants, herbivores and their natural enemies along a grassland management gradient 2008. 54660 records from MfN - Fossil Fish Collection. 2 records from Rediscovery of Terebratulina austroamericana Zezina, 1981 (Brachiopoda: Cancellothyrididae) from off northern Chile. 528 records from Données Rhopalocères et Zygènes du GIRAZ - export réalisé pour le pré-Atlas régional en 2016. 18 records from Lambillionea. 14 records from A new species of genus Nishada Moore, 1878 (Lepidoptera, Erebidae, Arctiinae) from India. 6162 records from Flore des Pyrénées. 7 records from Review of Scydmaenus (Geoscydmaenus) of Madagascar (Coleoptera, Staphylinidae, Scydmaeninae). 920 records from Morphological revision of the hyperdiverse Brueelia - complex (Insecta: Phthiraptera: Ischnocera: Philopteridae) with new taxa, checklists and generic key. 46600 records from Central African Plants. 52370 records from Données de Mammifères enregistrées dans BazNat - Lot 1. 128 records from Ectomycorrhiza species in a soil exchange experiment. 360 records from Priority Invasive Species in Tafea Province, Vanuatu. 14 records from Micralestes (Characiformes, Alestidae) of the lower Congo River, with a description of a new species endemic to the lower Congo River rapids in the Democratic Republic of Congo.. 6164 records from Antarctic, Sub-Antarctic and cold temperate echinoid database. 55434 records from Données naturalistes de Arnaud HORELLOU. 1875 records from Estimación del tamaño de la población anidadora de tortuga laúd Dermochelys coriacea y su distribución en el Pacífico mexicano durante la temporada de anidación 1996-1997. 334 records from Taxonomic revision of the Palaearctic Tetramorium chefketi species complex (Hymenoptera: Formicidae).. 33357 records from Données naturalistes d'Anthony TURPAUD. 60561 records from Alterra (NL) - Entomofauna inventory in riverside grasslands. 5774 records from Enquête participative "Lichens forestiers d'Auvergne et du Massif Central". 1575 records from Complex diversity in a mainly tropical group of ant parasitoids: Revision of the Orasema stramineipes species group (Hymenoptera: Chalcidoidea: Eucharitidae). 81 records from An annotated checklist and key to the Bulgarian cockroaches (Dictyoptera: Blattodea). 12 records from Notes on the genera Antinia Pascoe, 1871 and Dermatodina Faust, 1895 with description of D. boroveci sp. nov. from Thailand (Coleoptera: Curculionidae: Entiminae). 4 records from Description of two new species of the Neoperla montivaga group (Plecoptera: Perlidae) from Guangxi Zhuang Autonomous Region, China. 1271 records from Zooplankton Bering Strait Tiglax 1991. 7 records from The FranKliniella fauna of Brazil: additions and updated key to species (Thysanoptera: Thripidae). 12909 records from Odonata Collection. 298 records from Museu Paraense Emilio Goeldi - Amblypygi Collection. 1124 records from Distribution of Water Voles in Greater Manchester. 182 records from Phytoseiid mites (Acari: Phytoseiidae) associated with tropical ornamental plants, with a checklist and a key to the species of Bahia, Brazil. 46017 records from Colección Entomológica de Piedras Blancas. 48537 records from Fusión y actualización de las bases de datos del Herbario de la Facultad de Ciencias, UNAM (FCME), Guerrero. 3 records from Genera of Mythicomyiidae (Insecta, Diptera) new to the fauna of Morocco, with descriptions of new species. 53886 records from Collections of Phytoplankton at BGBM. 1782 records from (Table 14B) Occurrences of planktonic foraminifers in DSDP Hole 592, samples 592-30-CC through 592-41-CC. 120 records from The ant genus Linepithema (Formicidae: Dolichoderinae) in Colombia. 110 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 396 records from Moorea Biocode : Mollusques terrestres et aquatiques. 213 records from Reef fish species from Vava’u archipelago, Tonga, 2014. 30418 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleovertebrates National Collection (MACNPv). 680744 records from Observatoire LPO Franche-Comté des espèces (oiseaux, amphibiens, reptiles, mammifères sauf chauve-souris). 78 records from Inventaire des oiseaux sur le territoire de la métropole Rouen Normandie. 189 records from SuLaMa yam occurence data. 2 records from Macrocyrtus imomzodai Barševskis, 2016, a new synonym of Metapocyrtus (Orthocyrtus) orbiferoides Schultze, 1918 (Coleoptera: Curculionidae: Entiminae). 3902 records from SEWBReC Myriapods, Isopods, and allied species (South East Wales). 1516 records from (Table 13) Benthic foraminifera in early-mid Miocene sediments of DSDP Hole 90-592. 189 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Podicipedidae. 2 records from Synthèse de la Répartition des populations de chamois en 1994 (réseau Ongulés sauvages ONCFS-FNC-FDC). 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 101 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2010. 184 records from A review of the Stenus viridanus group (Coleoptera, Staphylinidae) from China with descriptions of two new species. 8 records from A new species of Pachyurus Agassiz 1831 (Teleostei: Perciformes: Sciaenidae) from the Río Napo basin, Eastern Ecuador.. 2130 records from Nudibranchs of the Sunshine Coast Australia. 4 records from Données naturalistes de Jean-Philippe SIBLET. 15 records from Redescription of Pseudotropheus livingstonii and Pseudotropheus elegans from Lake Malaŵi, Africa. 6 records from A new species of Amolops (Anura: Ranidae) from southwestern Guangdong, China. 498 records from A revision of the spider genus Zaitunia (Araneae, Filistatidae). 204084 records from New Zealand Fungal and Plant Disease Collection (PDD). 294 records from (Figure 4) Distribution of dinoflagellates in ODP Hole 129-802A. 42 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Passeridae. 1924 records from (Table T1) Abundance of stratigraphically important planktonic foraminifera in ODP Site 186-1150 sediments. 7671 records from Conservación de la guacamaya verde (Ara militaris) en la Reserva de la Biosfera Tehuacán Cuicatlán, México (segunda fase). 10 records from Notes on the genus Yunnantettix Zheng (Tetrigidae: Cladonotinae), with descriptions of two new species from Thailand. 2122 records from Antarctic Biodiversity Studies 2006 (Ross Sea, Scott Island, and Balleny Islands) (TAN0602). 4728 records from David Dodds Associates Ltd - Species Records. 80 records from Palynomorph data and remarks on dominant tree taxa from IODP Hole 313-M0029A. 3890 records from (Appendix 1) Calcareous nannofossils in ODP Hole 119-738B. 16098 records from The BCT/MTUK Bats & Roadside Mammals Survey. 45 records from Seven new species of Loneura Navás (Insecta: Psocodea: ‘ Psocoptera’: Ptiloneuridae) from Valle del Cauca, Colombia. 48 records from A new species of Bedotia (Teleostei: Atherinomorpha: Bedotiidae) from the Rianila drainage of Eastern Madagascar, with redescriptions of Bedotia madagascariensis and Bedotia geayi.. 24 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Phalacrocoracidae. 2714 records from Plume moths - ANIC. 192302 records from Limnic freshwater pelagic invertebrates biogeographical mapping/inventory NTNU University Museum. 8 records from Simpsonichthys nielseni sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the São Francisco River basin, Brazil.. 4 records from Zooplankton abundance measured on water bottle samples during Jan Mayen cruise JM6. 384145 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 4534 records from Melbourne Water Frog Census. 6810 records from Esponjas, corales escleractinios, equinodermos y peces de arrecifes coralinos del norte y sur de Veracruz. 1098 records from The Wildlife Information Centre - BioBlitz Events. 1671 records from EXPLOR'NATURE 2017, inventaire biologique de la commune de Barcelonette. 946 records from DMNS Parasite Collection (Arctos). 198 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en el Parque Provincial Salto Encantado (Guller et al.a, marzo 1997). 4 records from High-resolution X-ray computed tomography of an extant new Donuea (Araneae: Liocranidae) species in Madagascan copal. 528 records from Mamíferos de Colombia. 2138 records from Pollen analysis of sediment profile BUA1 from Buchsee. 1140 records from Loup 2014 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 50 records from Two new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from South America. 184756 records from E. C. Smith Herbarium (ACAD). 3999 records from Sistematización de la colección de peces del centro de México. 12480 records from Herbario de Briófitos de la Universidad de Salamanca: SALA-Bryo. 3 records from New data on the taxonomy, ecology, and conservation of the rediscovered Louisea edeaensis (Bott, 1969) (Brachyura: Potamoidea: Potamonautidae), an endangered freshwater crab from Cameroon. 14423 records from Naturhistorisches Museum Mainz, Herbarium von Ruprecht Düll. 28384 records from CSIRO, fish surveys by the Courageous, 1978-1979. 22 records from A new genus and three new species of nemacheilid loaches from northern Irrawaddy drainage, Myanmar (Teleostei: Cypriniformes). 47296 records from WTSWW Data: All Taxa (West Wales). 81 records from Description of one new genus and four new species of mynoglenine spiders from Africa (Araneae: Linyphiidae: Mynogleninae). 43988 records from Lichen herbarium, Tromsø Museum. 608 records from Données naturalistes d'Eléonore VANDEL. 78 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 179 records from Bureau_des_Guides_Naturalistes_2017_12_18. 3018 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 12 records from The African species of the subfamily Penestominae (Araneae: Eresidae): with descriptions of two new species. 2 records from Oribates mollicomus. 144614 records from Reef Life Survey - Survey Records. 795 records from AGRESTIS_2017_12_18. 9 records from Seodaemun Museum of Natural History Mammal. 1032 records from Fungal specimens of Komatsu City Museum. 3640 records from (Table 4) Pleistocene nannofossil range chart for ODP Hole 134-827A. 22 records from Données naturalistes de François BOCA. 2360 records from Données Rhopalocères et Zygènes de la RNN Cousseau - export réalisé pour le pré-Atlas régional en 2016. 3670 records from ARKO Overvåking kalklindeskog. 1165 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 50 records from Species delimitation of colour polymorphic Cladophorus (Coleoptera: Lycidae) from New Guinea. 1188 records from (Table T2) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1209A, Shatsky Rise, Pacific Ocean. 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 214 records from Notoaturine water mites from New Zealand (Acari: Hydrachnidia: Notoaturinae) with the description of five new species. 560 records from Australian National Insect Collection - Euryglossinae Bee Expedition 1:. 3 records from First record of the subgenus Duolandrevus (Duolandrevus) (Orthoptera: Gryllidae: Landrevinae) from China, with description of a new species. 10 records from Two New Species Of The Genus Oedignatha Thorell (Araneae: Clubionidae) From Coastal Andhra Pradesh, India. 114 records from Jeu de données convention golf de Vidauban 2016-2022. 32236 records from imr_mareano_rpsledge. 60 records from New species of Lachesilla (Psocodea: Psocomorpha: Lachesillidae), in species group corona, from southern Mexico and Central America. 468 records from Zooplankton and Ichthyoplankton Data Collected from the Chukchi and Beaufort Seas during the R/V Mirai Cruise, September 2002. 12 records from Systematic studies of the genus Aegialomys Weksler, Percequillo and Voss, 2006 (Rodentia: Cricetidae: Sigmodontinae): Annotated catalogue of the types of the species-group taxa. 10000 records from Actualización de la base de datos computarizada de la colección ictiológica de la Universidad Autónoma de Baja California. 22 records from Subantarctic Fur sealsat Heard Island, 1987/88. 273 records from (Table 1) Middle Eocene silicoflagellates from DSDP Hole 95-612. 28 records from Descriptions of new and little-known land snail taxa from Turkey, and establishment of a new genus (Gastropoda, Pulmonata: Lauriidae, Enidae and Vitrinidae). 14 records from Species groups in the genus Atrocrates Koch, 1956 (Coleoptera: Tenebrionidae: Pedinini). 27 records from Cleaning old cabinets: revealing the taxonomy of Sri Lankan wolf spiders (Araneae, Udubidae and Zoropsidae). 108 records from Herbier de l'Ecole Normale de Bourges (BOUM). 132 records from New Black Fungus Gnats (Diptera, Sciaridae) of North America Part I. Genus Scatopsciara Edwards, 1927. 172 records from UWIZM Cnidarians. 732 records from A revision of the Neogene Conidae and Conorbidae (Gastropoda) of the Paratethys Sea. 829 records from Colección Ornitológica Universidad de Nariño. 6 records from First record of Viannaiidae (Nematoda: Trichostrongylina) in fossorial rodents (Ctenomys spp.) from Central Argentina, with description of a new genus and species. 6060 records from Herbario virtual bosques secos de Colombia - Sección herbario TULV (INCIVA). 10 records from Tracking saltwater crocodiles on the Wenlock River, Cape York, Queensland, Australia 2012_13. 2 records from Carabodes cephalotes. 12 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 1605 records from Phytoplankton measured on water bottle samples during THALASSA cruise PROSOPE. 147 records from Additional records for Stenosagola newtoni Park & Carlton, 2013 (Staphylinidae: Pselaphinae: Faronitae), with notes on aedeagal morphology. 7 records from Characterization of Platymessa with redescription of the type species and a new generic synonymy (Arachnida, Opiliones, Cosmetidae). 22 records from Review of the genus Trichiotes Casey (Coleoptera: Tenebrionidae: Pimeliinae: Edrotini), with the description of a new species and a preliminary checklist of the Tenebrionidae from Cuatrociénegas, Mexico. 10 records from Review of Nilodosis Kieffer (Diptera: Chironomidae: Chironominae), with description of a new species from South China. 4 records from Molecular phylogeny, morphology and taxonomy of Moroccan Triops granarius (Lucas, 1864) (Crustacea: Notostraca), with the description of two new species. 4811463 records from Relevés floristiques du protocole de l'Inventaire National Forestier de l'IGN. 1619 records from Canadian Museum of Nature Fossil Invertebrate Collection. 432 records from Monitoreo biológico en la cuenca Dagua - Subcuenca La Guinea ARA - RARE - CVC – Asociación Calidris. 33 records from Taxonomic status of maskrays of the Neotrygon kuhlii species complex (Myliobatoidei: Dasyatidae) with the description of three new species from the Indo-West Pacific. 27 records from First detection of the adventive large rove beetle Ocypus nitens (Schrank) in Canada and an update of its Nearctic distribution using data generated by the public. 46 records from New species and new records of the family Laelapidae (Acari: Mesostigmata) from Republic of Korea. 1510 records from Helgeland Museum, Syrphidae. 19 records from Tyrannosaurids (Dinosauria) of Asia and North America. 16 records from New species of Endecous (Grylloidea, Phalangopsidae, Luzarinae) from the Iguaçu National Park (Brazil), including bioacoustics, cytogenetic and distribution data. 14373 records from Collection des données de biodiversité marine de Nouvelle-Calédonie - IRD Nouvelle-Calédonie. 4 records from Bucardium grateloupianum n. sp. from the Lower Miocene of Aquitaine with taxonomic comments on some fossil species from Europe (Bivalvia, Cardiidae). 4 records from Gymnothorax hansi, a new species of moray eel (Teleostei: Anguilliformes: Muraenidae) from the Comoro Islands, Western Indian Ocean.. 3 records from Designation Of Lectotypes For The Mexican Species Of Andricus Described By Alfred Kinsey And Comments About Some Generic Synonymies (Hymenoptera: Cynipidae). 3835 records from (Table T1) Planktonic foraminifera abundance of ODP Site 170-1039 sediments. 39 records from A new species of the genus Phytoecia Dejean, 1835 (Coleoptera: Cerambycidae) from Greece. 10 records from A new species of Phaenostoma d’Orchymont, 1937 (Coleoptera: Hydrophilidae) from Brazil. 769 records from Insectos de los Parques Ecológicos Distritales Humedales de Bogotá, D.C.. 12 records from The sea lice (Copepoda: Caligidae) of Moreton Bay (Queensland, Australia), with descriptions of thirteen new species. 4000 records from Diversidad y distribución de los copépodos (Cyclopoida) de las zonas áridas del Centro-Norte de México. 165 records from Occurrence of zoobenthos organisms in the sampled Central-Yakutian Lakes, Appendix 2-4. 205 records from Aves del municipio El Carmen de Chucurí, Santander - Proyecto Santander BIO. 127 records from Kieppi mammals collection. 39946 records from Natusfera Citizen Science Observation Dataset. 43 records from Species of Wadicosa (Araneae, Lycosidae): transfer of two species from Pardosa and description of three new species from Africa. 212 records from Revision of the genus Dinotoperla Tillyard, 1921 (Plecoptera: Gripopterygidae) using morphological characters and molecular data: Establishes two new genera, three new species and updates the larval taxonomy. 132727 records from African Plants - a photo guide. 1500 records from Amphibian and Reptilian (ENHM-AR). 2286 records from Fauna acuática de importancia ecológica (crustáceos, insectos y peces) de la cuenca del río Moctezuma Querétaro-Hidalgo. 8988 records from University of Amsterdam (NL) - Páramo Vegetation Research, Sumapaz-Bocagrande-Chisaca paramo complex, Colombia. 177838 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 4 records from Morphology and systematic position of Cingula tumidula G. O. Sars, 1878 (Gastropoda: Rissoidae). 14304 records from Conventions d’étude sur la biodiversité française – Partenariats du SPN. 2 records from Nothrus gibbus. 90 records from New records of millipedes and centipedes from Bulgaria, with an annotated checklist of the Bulgarian myriapods. 45 records from Caracterización Ecológica de la avifauna del Cerro Jánano. 46 records from Coleção de Brachiopoda do Museu Nacional - UFRJ. 61 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 12 records from On the new monotypic wolf spider genus Ovia gen. nov. (Araneae: Lycosidae, Lycosinae). 1144 records from (Table 1) Distribution of upper Campanian-lower Maestrichtian calcareous nannofossils at DSDP Hole 71-511. 139 records from (Table T4) Abundance of foraminifers and presence of other fragments in ODP Hole 188-1166A sediments. 7 records from On the identity of some poorly known species of the genus Endonura Cassagnau, 1979 (Collembola, Neanuridae, Neanurinae). 729 records from Las tortugas marinas y sus playas de anidación en México. 6 records from New species of the spider genus Olios Walckenaer, 1837 (Araneae: Sparassidae: Sparassinae) from Laos. 26 records from Lerneca inalata beripocone subsp. nov. (Orthoptera: Phalangopsidae; Luzarinae): a new taxon for the northern Pantanal of Brazil. 6 records from Eodromyia pumilio gen. et sp. nov., a new empidoid fly from the Earliest Eocene amber of France (Diptera: Hybotidae: Tachydromiinae). 15 records from A new species of iguana Brachylophus Cuvier 1829 (Sauria: Iguania: Iguanidae) from Gau Island, Fiji Islands. 2 records from Arthropoden aus südostalpinen Höhlen.. 240844 records from Occurrences in SinBIOTA. 6 records from Doryphoribius chetumalensis sp. nov. (Eutardigrada: Isohypsibiidae) a new tardigrade species discovered in an unusual habitat of urban areas of Mexico. 5936 records from Los crustáceos decápodos marinos: Actualización de la colección carcinológica de la Facultad de Ciencias Biológicas, UANL. 10197 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 2500 records from Crustáceos macrobénticos de la plataforma y talud continental del Golfo de México. 1 records from A new record of Potamanthellus caenoides Ulmer 1939 (Ephemeroptera: Neoephemereidae) from the southern Western Ghats of India. 75 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 3510 records from (Table 2) Benthic isopod species of the Ross Sea, their bathymetry and distribution in the Southern Ocean. 28 records from Three new species of Coccophagus (Hymenoptera: Aphelinidae) from China, with new distributional data for three additional species. 160 records from Billards A. 1936. Les fonds de peches pres d Alexandrie. VI Hydroidea. Notes et memoires No 13. 1 records from A new species of small-eared shrew of the genus Cryptotis (Mammalia, Eulipotyphla, Soricidae) from the northernmost Peruvian Andes. 493794 records from Mycology herbarium, Oslo (O). 14340 records from The Bergius Herbarium. 753 records from PSU-Seaweed Collection. 312 records from Données naturalistes de NOËL Rémi. 146 records from Rhopalocères du PNR Périgord Limousin au 15/10/2015. 20 records from Colección de Referencia de Anfibios del Museo de Ciencias de la Universidad El Bosque. 110996 records from Wikiplantbase #Liguria. 567529 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 25041 records from Rare and Protected Species Records Across Wales 1975 to 2012. 14 records from Two new species in the annelid genus Stygocapitella (Orbiniida, Parergodrilidae) with comments on their biogeography. 3 records from Aeolothrips neyrizi, a new species of the genus Aeolothrips (Thysanoptera: Aeolothripidae) from southern Iran. 5960 records from Poliquetos litorales de la región norte y centro del estado de Veracruz. 22 records from Etmopterus burgessi sp. nov., a new species of lanternshark (Squaliformes: Etmopteridae) from Taiwan.. 12 records from A new species of Eurypeza Lacroix, 2006 (Coleoptera: Scarabaeidae: Melolonthinae: Tanyproctini) from Kenya. 41 records from Support for the underrepresented sex: new descriptions of scutacarid males (Acari, Heterostigmatina). 4376 records from Aspectos biológicos e impacto socio-económico de los plecos del género Pterygoplichthys y dos cíclidos no nativos en el sistema fluvio lagunar deltaico Río Palizada, en el Área Natural Protegida Laguna de Términos, Campeche. 388392 records from Mollusc (marine) data for Great Britain and Ireland. 1111260 records from Vascular Plant Herbarium, Oslo (O). 297 records from G.B. Pant Institute of Himalayan Environment & Development - Plants of West Himalaya, India. 2 records from Notizen über Oribatei (Acari). III. 12208 records from Guadeloupe_Insectes. 18 records from Agroeca dentigera and Entelecara omissa (Araneae: Liocranidae, Linyphiidae), found in Sweden. 108 records from Evaluación de la situación de Tillandsia mauryana en el Apéndice II de la CITES, según su estado de conservación y comercio. 1730782 records from WildNet - Queensland Wildlife Data. 16329 records from Orchid Herbarium Collection. 2180 records from Diversidad biológica y conservación del ecosistema de los perros llaneros (Cynomys ludovicianus) en México. 198 records from Sauvegarde de la flore menacée de l'atoll soulevé de Anaa et définition de zones prioritaires de conservation basées sur la flore et la faune : données sur les Mollusques terrestres et aquatiques. 8 records from Taxonomic review of the Genus Tautoneura Anufriev (Hemiptera: Auchenorrhyncha: Cicadellidae: Typhlocybinae) from Korea, with description of one new species. 94 records from Taxonomic status of the Guadalupe Darter, Percina apristis (Teleostei: Percidae).. 8216 records from La Planète Revisitée, massif du Mitaraka, mission principale (février-mars 2015). 92 records from Pygmy grasshoppers (Orthoptera: Tetrigidae) of Vietnam: the genus Bolivaritettix Günther, 1939. 4410 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Actuopalynology National Collection (BAPa). 39 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cracidae. 2 records from A new bamboo-feeding species of Kaochiaoja Tao (Hemiptera: Aphididae) from India. 14 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 16812 records from Conservatoire Botanique Pierre Fabre. 46 records from Systematic position of the Afrotropical species described in Trachyphloeini (Coleoptera: Curculionidae: Entiminae). 36 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 285 records from Isotope tracer experiment: nematode isotope ratio. 31551 records from Atlas of Life in the Coastal Wilderness - Sightings. 23634 records from Données naturalistes de Cédric JACQUIER. 18 records from A new species of Theloderma (Amphibia: Anura: Rhacophoridae) from Vietnam. 1012 records from Butterflies of Guinea-Bissau: VIII. New data, new reports, corrections and biodiversity (Lepidoptera: Papilionoidea). 391220 records from Questagame weekly feed. 10 records from Les Sparteinae de Mayotte (Araneae, Salticidae). 16 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 32 records from New fossil gastropod species (Mollusca: Gastropoda) from the upper Miocene of the Canary Islands (Spain). 23576 records from Records of the Australian National Botanic Gardens Seedbank. 208 records from pandalidae-tychan-most. 7 records from Germalna, a new genus for the New Caledonian cicada previously assigned to the genus Melampsalta Kolenati, plus a complement to the description of the genus Rouxalna Boulard, with the description of two new species (Insecta: Hemiptera, Cicadoidea, Cicadidae). 2148 records from Monitoreo y uso del hábitat de aves neárticas y neotropicales asociados a ambientes acuáticos litorales en el municipio de Tomatlán, Jalisco, México. 4350 records from Colección Zoológica de la Universidad del Tolima (CZUT) - Ornitología. 12 records from Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand. 1048 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 130-806B. 360 records from (Figure 1c) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3192. 258 records from Marine tardigrades of the Bahamas with the description of two new species and updated keys to the species of Anisonyches and Archechiniscus. 62 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 15609 records from Enquête nationale participative sur l'écureuil roux. 20 records from Nesting biology of Paragymnomerus signaticollis tauricus (Kostylev, 1940) (Hymenoptera: Vespidae: Eumeninae). 15 records from New species of glass knifefish Eigenmannia loretana (Gymnotiformes: Sternopygidae) from the Western Amazon. 8 records from Taxonomic changes in Salyavatinae (Heteroptera: Reduviidae), with an updated generic key. 2603 records from Museu Paraense Emílio Goeldi - Paleoinvertebrate Collection. 10 records from Two new subfamilies, three new species and a new subspecies of dendrochirotid sea cucumbers (Echinodermata: Holothuroidea). 20 records from A new species of Miroculis Edmunds, 1963 (Ephemeroptera: Leptophlebiidae) from Cerrado-Amazonian forest transition zone, Brazil. 8 records from Tropidomyrmex elianae, a new myrmicine ant genus and species from Brazil, tentatively assigned to Solenopsidini (Hymenoptera, Formicidae).. 555200 records from UB - Herbário da Universidade de Brasília. 6 records from New species of Chnoodes Chevrolat (Coleoptera: Coccinellidae) from French Guiana. 2018 records from Données naturalistes de Daniel PAVON. 3418 records from The Gibson spider collection. 534 records from Die Milbenfauna der Nordseeinsel Wangerooge. 33819 records from Ecofact. 10 records from Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 18 records from A review of Newportia species in the subgenus Newportides Chamberlin, 1921 (Scolopendromorpha, Scolopocryptopidae, Newportiinae). 73 records from Blue Tier. 8 records from A new species and a new record of Sinella Brook (Collembola: Entomobryidae) from Guizhou Province, China. 202 records from The genus Setodes Rambur (Trichoptera, Leptoceridae) in Japan. 298456 records from Natural History Museum Rotterdam (NL) - Insecta collection. 64 records from Caracterización Floristica del Paramo de Frontino o del Sol. 4 records from A new species of Boulengerula Tornier, 1896 (Amphibia: Gymnophiona: Herpelidae) from Kenya and the “ rediscovery ” of Boulengerula denhardti. 93 records from Five new species of Geranomyia Haliday, 1833 (Diptera, Limoniidae) from China. 1314 records from Occurrence data of woody plants in the Ginkakuzi-san National Forest. 769 records from Digital Florula - Palo Verde Biological Station. 3110 records from Countryside Council for Wales - Bat Roosts Database - Pembrokeshire. 8040 records from Bryophyte specimens of Toyama Science Museum. 2 records from A new species of Asphinctopone (Hymenoptera: Formicidae: Ponerinae) from Tanzania.. 121 records from Données d'observations de cétacés par le GECEM de 2009 à 2012. 8824 records from Las monocotiledóneas mexicanas, una sinopsis florística. Parte II. 252 records from Kelp rafts in the Southern Ocean. 87 records from On Chilean Loxosceles (Araneae: Sicariidae): first description of the males of L. surca and L. coquimbo, new records of L. laeta and three remarkable new species from coastal deserts. 6 records from A new species of Stenchaetothrips (Thysanoptera, Thripidae) from Bamboo, based on morphological and molecular data. 40 records from Description of a new species of the genus Caeneressa from China, with a checklist of the genus (Lepidoptera: Erebidae). 2108 records from Mound building termites contribute to savanna vegetation heterogeneity- woody plants, forbs and graminoids. 9 records from Casuarinicola australis Taylor, 2010 (Hemiptera: Triozidae), newly recorded from New Zealand. 221 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Turdidae. 26 records from Caracterización de la avifauna presente en el río Tutunendo, Municipio de Quibdó-Chocó. 14886 records from Free-living marine Nematodes from San Antonio bay (Río Negro, Argentine) 2009.. 6042 records from (Table T2) Calcareous nannofossil stratigraphy of ODP Hole 198-1214A. 15979 records from (Appendix) Distribution of planktonic foraminifers at DSDP Hole 72-516F, Coniacian-Santonian to upper Maestrichtian. 8 records from Simonachorutes, a new genus of Pseudachorutinae (Collembola, Neanuridae) from Europe. 396 records from (Table AT9) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134B. 1564 records from Stonefly (Plecoptera) records from Britain and Ireland, via iRecord. 62428 records from Microlepidoptera of Glamorgan. 8 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 75 records from Worldwide revision of the genus Fraseroscyphus Boero and Bouillon, 1993 (Cnidaria: Hydrozoa): an integrative approach to establish new generic diagnoses. 151 records from World review of the genus Strongylophthalmyia Heller (Diptera: Strongylophthalmyiidae). Part I: Introduction, morphology, species groups, and review of the Strongylophthalmyia punctata subgroup. 105 records from Review of the genus Habropogon Loew, 1847 (Diptera: Asilidae) from Russia, with description of new species from Siberia. 4428 records from White shark tagging off New Zealand. 36 records from World’s northenmost and rarely observed Nudibranchs: three new Onchidoridid species (Gastropoda: Doridida) from Russian seas. 2544 records from Ecología y manejo de ungulados cinegéticos en el sur de Baja California Sur. 676 records from Código de barras genético de cinco grupos críticos de la flora de México. 68 records from Données d'observation opportunistes collectées par la Réserve Naturelle Nationale de l'Ile du Grand-Connétable et le Groupe d'Etude et de Protection des Oiseaux en Guyane. 19434 records from National System of Protected Areas in Poland - Animals. 5754 records from Listado anotado de los tiburones, rayas y quimeras (Chondrichthyes, Elasmobranchii, Holocephali) de México. 2880 records from Museum TwentseWelle (NL) - Fossil Ammonites Collection. 4 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 46644 records from Atlas der Raubfliegen Deutschlands - database. 2466148 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 2 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 891 records from Caracterización biológica de la ventana de biodiversidad municipio de Filandia, Quindío, Colombia. 2644 records from Records from the South Australian Seed Conservation Centre. 45 records from Seven new species of Strongylophthalmyia Heller, 1902 (Diptera: Strongylophthalmyiidae) from the Eastern Palaearctic and Oriental Regions with notes on peculiar rare species. 12 records from The genus Thelepus Leuckart, 1849 (Annelida, Thelepodidae) in Brazil, with a redescription of the holotype of T. setosus (Quatrefages, 1866). 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 76 records from Revision of the South American grassland leafhopper genus Cortona Oman (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with description of four new species from Argentina. 17582 records from Inventario de la lepidopterofauna de la Sierra de Huautla. 4 records from A new species of the genus Xysticus C. L. Koch from Turkey (Araneae: Thomisidae). 76 records from Five new species of the damselfish genus Chromis (Perciformes: Labroidei: Pomacentridae) from deep coral reefs in the tropical western Pacific. 51309 records from BCCM/LMG Bacteria collection. 14003 records from Données naturalistes de Patrick HAFFNER. 795 records from Fotografía digital para el estudio del impacto del cambio climático en la biodiversidad. 4 records from Four new generic and 14 new specific synonymies in Pholcidae, and transfer of Pholcoides Roewer to Filistatidae (Araneae). 39858 records from Global compendium of Aedes aegypti occurrence. 2869 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1995-1999. Part 1. 6 records from The mythic species Issus analis Brullé, 1833 (Hemiptera, Fulgoroidea, Issidae): still an enigmatic taxon. 70 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 2619 records from Caire-Chabrand Collection. 42 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 543 records from New data on spiders (Aranei) from the Maritime Province, Russian Far East. 182355 records from Distribution of Higher Plants in Greater Manchester. 4256 records from Freshwater Pest Plants. 9279 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 25592 records from Herbarium Amazonense. 4 records from Pseudoleptonema tansoongnerni new species (Hydropsychidae: Trichoptera) with species list of Trichoptera from Li Phi Falls, Mekong River, southern Laos. 554 records from Prélèvements Cerf de Java en Nouvelle-Calédonie. CEN_Nouvelle-Calédonie. 1 records from A new species of Frankliniella with 7 - segmented antennae from Mexico (Thysanoptera, Thripinae). 4853752 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 112 records from Recensement "nids hirondelles". 8 records from Studies in Colombian Caelifera and adjacent territories: Ciglianacris, a new genus of Andean Melanoplinae (Orthoptera: Acrididae). 262624 records from AUM Fish Collection. 4 records from Description of the puparium of Hermetia pulchra (Diptera: Stratiomyidae) from Brazil. 20760 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments. 2 records from Oribates fusifer. 1950 records from ant-plant_symbioses. 2 records from Deux especes nouvelles pour la science du genre Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). - Two new species for the science in the genus Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). 1744 records from Colección de Entomología - Hymenoptera - Parasitica. 17 records from Description of a new species of Euptychia Hübner, 1818 (Lepidoptera: Nymphalidae: Satyrinae) from the western Andes. 58084 records from ZFMK Hymenoptera collection. 1220 records from Culture Collection of Microalgae and Zygnematophyceae Collection Hamburg (MZCH-SVCK). 8 records from On Plesionika persica (Kemp, 1925) and P. reflexa Chace, 1985 (Crustacea: Decapoda: Pandalidae) from India. 2728 records from (Figure 8c) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-536. 6 records from Type designations and taxonomic remarks for Nearctic sap beetles in the subfamily Carpophilinae Erichson (Coleoptera: Nitidulidae). 8 records from A new leaf-litter harvestman species of the genus Karos (Opiliones: Stygnopsidae: Karosinae), with a reanalysis of the morphological phylogeny of the genus. 889 records from (Table 4a) Miocene biostratigraphy of the Reinbekian stage in Schleswig-Holstein. 4556 records from Mammals in MZNA-VERT: project Human impacts in rivers of Navarra. 681 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 248 records from (Table S1) Distribution of Florisphaera profunda in surface sediment samples. 6 records from First description of the last instar larva and pupa of the aquatic crane fly Limnorimarga limonioides (Alexander, 1945) (Diptera: Limoniidae). 8014 records from DREAL_PACA_-_N2000_-_Communauté_d_Agglomération_Pays_de_Martigues_2017_12_18. 43326 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 3 records from Australnirvana, a new leafhopper genus of Nirvanini (Hemiptera: Cicadellidae: Evacanthinae) from Australia. 3 records from A new species of Hortipes (Araneae, Corinnidae), the Frst spider with an insertable retrolateral tibial apophysis on the male palp. 378 records from Observations diverses réalisées à l'occasion de l'inventaire entomologique des ZNIEFF de Martinique. 3750 records from Plant Observation Records of Japan. 13792 records from Registros de hongos en áreas protegidas de la Argentina. 9 records from Another alien on the horizon? First European record of Tautoneura polymitusa, an East Asian leafhopper (Hemiptera: Auchenorryncha: Cicadellidae). 1100 records from Colección de Referencia de Macroinvertebrados Bentónicos del Museo de Ciencias de la Universidad El Bosque. 4 records from Remarks on Oriental species of Allophrys Förster described by A. Reshchikov (Hymenoptera: Ichneumonidae: Tersilochinae). 26 records from Another new species of Phyllodytes (Anura: Hylidae) from the Atlantic Forest of northeastern Brazil. 324 records from Données naturalistes d’Alexandre CREGU. 6 records from Scolionema sanshin sp. n., a new species (Hydrozoa, Limnomedusae, Olindiidae) from the Ryukyu Archipelago, southern Japan. 3 records from First description of the male of the easternmost Harpactea species, H. parthica (Araneae: Dysderidae). 110 records from A taxonomic revision of the Pheidole roosevelti-group (Hymenoptera: Formicidae) in Fiji.. 32 records from A review of the gobiid genus Akko (Teleostei: Gobiidae) with description of a new species.. 44 records from Synonymy of Homalopoltys (Araneae: Araneidae) with the genus Dolichognatha (Araneae: Tetragnathidae) and descriptions of two new species. 6 records from Trichomycterus giganteus (Siluriformes: Loricarioidea: Trichomycteridae): a new catfish from the Rio Guandu basin, southeastern Brazil.. 8892 records from Liverworts (Marchantiopsida) and Hornworts (Anthocerophyta) of Denmark. 15 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 302668 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 12425 records from Herbario virtual bosques secos de Colombia - sección herbario FMB (IAvH). 58789 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 212 records from Anfibios y reptiles de la sierra de Cuatro Venados, Oaxaca, México. 10 records from Redescription of a little-known spider species, Mesiotelus lubricus (Simon, 1880) (Aranei: Liocranidae) from China. 640 records from Ants: Formica Exsecta Records from Abernethy RSPB. 133 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Parulidae. 2 records from Description of a second species of the genus Moronius Grossi & Vaz-de-Mello, 2015 (Coleoptera: Scarabaeidae: Rutelinae: Rutelini). 152 records from Colección de Referencia de Cnidarios del Museo de Ciencias de la Universidad El Bosque. 7160 records from South Australian Museum Terrestrial Invertebrate Images. 185 records from Spiders from Laos with descriptions of new species (Arachnida: Araneae). 62 records from Studies in Liocranidae (Araneae): redescriptions and transfers in Apostenus Westring and Brachyanillus Simon, as well as description of a new genus. 80 records from Review of the Alompra ferruginea Moore, 1872 complex with description of a new species from Taiwan (Lepidoptera, Lasiocampidae). 6 records from Two new species of Miltochrista from India (Lepidoptera, Erebidae, Arctiinae). 8 records from Two new species and records of Olophrum laxum species group (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) from China and Nepal. 1872 records from Herbier National de Guinée (HNG). 12 records from (Table 1) Beluga (Delphinapterus leucas) sightings in the eastern Beaufort Sea. 597 records from Greenland macrobenthos 2006. 116 records from Undercover speciation of wentletraps (Caenogastropoda: Epitoniidae) in the Southwestern Atlantic. 1597 records from Inventaires PnrL "Etangs". 4 records from Immatures of Cerambycinae (Coleoptera, Cerambycidae) collected in Litchi chinensis Sonn. (Sapindaceae) in Brazil. 1164 records from Estatus ecológico y distribución de la ictiofauna de humedales costeros (bocanas y marismas) en el noroeste de Baja California México (Área marina prioritaria amenazada A1: Ensenadense). 2906 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales de afloramiento rocoso del Parque Nacional Natural El Tuparro. 456 records from On the genus Trachysalambria Burkenroad, 1934 (Crustacea, Decapoda, Penaeidae), with descriptions of three new species. 24 records from Five new records of marine shrimps (Decapoda: Caridea, Stenopodidea) from the Caribbean coast of Panama. 20 records from Two new species of eelpouts (Teleostei, Zoarcidae) of the genus Seleniolycus from the Ross Dependency, Antarctica.. 4 records from Neotype Designation for Aedes (Stegomyia) albopictus (Skuse). 12 records from Phonognatha vicitra Sherriffs, 1928 - a taxonomic misidentification of the orb-weaving spider Acusilas coccineus Simon, 1895 (Araneae, Araneidae). 154470 records from Vascular plant specimens of Nagano Environmental Conservation Research Institute, Nagano Prefecture. 2842 records from Weevils of Poland. 10 records from A new diploid species belonging to the Odontophrynus americanus species group (Anura: Odontophrynidae) from the Espinhaço range, Brazil. 4230 records from Araneae_Raw1. 2 records from Nothrus posticus. 210 records from Species Surveillance Project - In-House Pilots records for 2012. 55 records from The world fauna of Synchroidae Lacordaire, 1859 (Coleoptera, Tenebrionoidea, Synchroidae). 4 records from Two new species of brackish-water Macrostomum (Platyhelminthes, Macrostomida) from southern China. 1239 records from (Appendix Table 2) Relative abundances of calcareous nannofossil in the >4 µm assemblage of ODP Hole 177-1090D. 2982 records from Formación de las colecciones de referencia de aves y mamíferos de la Reserva de la Biosfera de Sian Ka'an, Quintana Roo, México. 8984 records from Plant specimens of Obihiro Centennial City Museum. 8230 records from Inventario florístico de la Reserva de la Biosfera Mariposa Monarca, México. 9 records from New records and updated checklist of Cicadomorpha (Hemiptera: Auchenorrhyncha) species from Greece. 824 records from Plants, Bryophytes and Lichens recorded on Quinag in 2006-2007. 24 records from A new genus of nesticid spiders from western European Peninsulas (Araneae, Nesticidae). 105224 records from Biodiversity Now / Nature Check (Biodiversitet Nu / NaturTjek). 2749 records from Miscellaneous Vascular Plants. 16992 records from RNF - LPO Rhône-Alpes. 23037 records from Herbier CNRST/INERA. 16478 records from Convention Suez Environnement (SITA) – SPN. 33089 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 548 records from Detection histories for eight species of Amazona parrots in Venezuela during the NeoMaps bird surveys in 2010. 96980 records from Actualización e incremento de la base de datos del Herbario de la Benemérita Universidad Autónoma de Puebla. 64 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 19 records from Five new species of the Clubiona corticalis species group (Araneae, Clubionidae) from China. 1596 records from Catálogo de las especies de crustáceos anfípodos invasores del Parque Nacional Sistema Arrecifal Veracruzano (PNSAV) y la actualización de la base de datos (CONABIO) de los anfípodos en México. 354988 records from Segundo censo de plantas leñosas de una Parcela Permanente de 25 hectáreas, ubicada en la Reserva Natural La Planada (Nariño, Colombia). 2202 records from Colección de Entomología - Orthoptera. 501 records from Morfología funcional de mantos de rodolitos en el golfo de California, México. 24211 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 40 records from Two new species of Curculionichthys (Siluriformes: Loricariidae) from the rio Amazonas basin, Brazil. 700 records from Speothos Venaticus por Guillermo Gil. 4521 records from Ecología, genética y conservación de la caoba (Swietenia macrophylla): herramientas para un manejo adaptativo de la selva Maya de Quintana Roo, México. 3700 records from Données diverses du PnrL. 48 records from (Table 1) Diving behaviour of male Adélie penguins (Pygoscelis adeliae) with and without corticosterone implants at Pointe Géologie. 9500 records from Plant specimens of Tama City Cultural Foundation. 5985 records from Monitoreo y morfometría de la avifauna de la Universidad del Valle 2011-2012. 12 records from ZUEC-API - Coleção de Apicomplexa do Museu de Zoologia da UNICAMP. 10 records from On the Cryptops subgenus Trichocryptops Verhoeff, 1937, with a discussion of the problems of differentiating Cryptops species (Chilopoda: Scolopendromorpha: Cryptopidae). 9358 records from Herbarium - Las Cruces Biological Station. 67569 records from RNF - CEN Nord-Pas-de-Calais. 5626 records from Amphibiens et Reptiles de Martinique (données Michel Breuil). 90 records from (Table 1) Beluga (Delphinapterus leucas) density and abundance, and pod characteristics in west Greenland waters. 2323899 records from Australian Museum provider for OZCAM. 1562 records from Bittern Annual Surveys in Britain 1990-2011. 15 records from Review of Acangassuini Galileo & Martins, 2001 (Insecta, Coleoptera, Cerambycidae), with description of a new genus and species, and description of two new species in the tribes Methiini Thomson, 1860 and Oemini Lacordaire, 1868. 82 records from First records of seven species of mantis shrimp from India (Crustacea: Stomatopoda). 703758 records from KUBI Herpetology Collection. 1897 records from Museu Paraense Emílio Goeldi - Paleovertebrate Collection. 486 records from Pollen analysis of sediment profile NMS0 from Neumühler See. 2045 records from Logan City Council Species Sightings. 9 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 4443 records from Leicestershire and Rutland Mature trees Inventory 2011. 48004 records from Actualización de la base de datos de la colección nacional de anfibios y reptiles (CNAR). 3 records from The millipede Typhloglomeris caucasica Golovatch, 1975 found epigeically (Diplopoda, Glomerida, Glomeridellidae). 3684 records from Inventaires malacologiques en Pays de Savoie. 36 records from BIOMEO_2017_12_18. 3 records from Cheiloneurus flaccus (Walker, 1847) (Hymenoptera: Encyrtidae), new to New Zealand. 945 records from Herbivorie_Pflanzenebene_2008. 14142 records from Colección de Anfibios. 76 records from A taxonomic review of the Korean species of the subgenus Datomicra Mulsant & Rey of the genus Atheta Thomson, with description of a new species (Coleoptera, Staphylinidae, Aleocharinae). 6 records from Revised morphology of Pycnonemosaurus nevesi Kellner & Campos, 2002 (Theropoda: Abelisauridae) and its phylogenetic relationships. 11554 records from Geologisch-Paläontologische Sammlung Universität Leipzig. 502 records from Colección Quirópteros Museo de La Salle Bogotá (MLS). 439 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 43647 records from Alterra (NL) - Comparison of entomofauna in four different habitats. 421 records from Spatial and seasonal variability of the molluscan macrofauna at the marine-lagoonal environmental gradient at Kalloni saltworks (Lesvos Island, NE Aegean Sea, Greece). 231 records from Terrestrial isopods of the genus Porcellio Latreille, 1804 (Isopoda; Oniscidea) in Iran, with a description of a new species. 122282 records from Canadian Museum of Nature Fish Collection. 24 records from E. E. Green’s collection of scale insects (Hemiptera: Sternorrhyncha: Coccomorpha) in The Natural History Museum, London, U. K.. 29613 records from Micro-moths distribution for Dumfries and Galloway. 379 records from Enquête DREAL Auvergne Bivalves. 142 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Ross Sea (Antarctica) collected by the New Zealand Antarctic expedition BioRoss 2004 with RV Tangaroa. 46664 records from Fife non-breeding bird 5km atlas 1991-99. 29829 records from (Table 2) Mollusc biostratigraphy of facies underlying the 'Braunkohlensande' in the Lauenburg district, north Germany. 16 records from Three new species and one new record of the leafhopper genus Agnesiella Dworakowska, 1970 (Hemiptera: Cicadellidae: Typhlocybinae: Typhlocybini) from China. 24 records from One new genus and three new species of plumulariid hydroids (Cnidaria, Hydrozoa, Plumulariidae) from the western Pacific Ocean, with a re-examination of Plumularia insignis Allman, 1883 and related taxa. 1239 records from (Table 3) Composition of turbidite and background samples at ODP Site 166-1003. 4 records from A supplement of the genus Diaphanogryllacris (Orthoptera: Gryllacridinae) from China. 33 records from New species of Chimerothalassius Shamshev & Grootaert (Diptera: Dolichopodidae: Parathalassiinae) from the West Indies and Costa Rica. 1236 records from Scottish Crossbill National Survey in the UK in 2008. 2 records from Caledomus gen. nov., a new cillaeine genus (Coleoptera, Nitidulidae) from New Caledonia and taxonomic notes. 16154 records from Occurrence Data of Vascular Plants from Abandoned Agricultural Fields (Moscow and Tula Regions, Russia). 1474 records from Données naturalistes de Thomas THERY. 26 records from SNH Invertebrate Site Condition Monitoring 2013/14: Loch Lubnaig Marshes SSSI. 2927 records from (Table 2) Live benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 6 records from Sinorhodeus microlepis, a new genus and species of bitterling from China (Teleostei: Cyprinidae: Acheilognathinae). 254 records from Collection Ephemeroptera - SMF. 105 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 26 records from A taxonomic review of the genus Astrodendrum (Echinodermata, Ophiuroidea, Euryalida, Gorgonocephalidae) with description of a new species from Japan. 2 records from Southern high latitude squat lobsters II: description of Uroptychus macquariae sp. nov. from Macquarie Ridge. 122 records from Population status, Distribution and Threats to the Nile lechwe (Kobus megaceros, M.T.Von Heuglin,1853) in the Sudd Wetland, South Sudan (2012). 10 records from Three new species of Lyssomanes HENTZ, 1845 from Peru (Arachnida: Araneae: Salticidae). 4854 records from Dataset of herbarium specimens of threatened vascular plants in Catalonia. 938 records from Collection Diptera - SMF. 36 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 2 records from Miriapodi di alcune grotte della Campania. 70 records from Mayflies of the genus Epeorus Eaton, 1881 s. l. (Ephemeroptera: Heptageniidae) from the Caucasus Mountains: a new species of Caucasiron Kluge, 1997 from Georgia and Turkey. 824 records from Bird specimens of Saitama Museum of Natural History. 740067 records from Mollusc (non-marine) data for Great Britain and Ireland. 4332 records from Diversidad de Mariposas en la Reserva Natural El Romeral. 303 records from Fauvel P. 1937. Les fonds de pèche près d'Alexandrie. XI.Annélides Polychètes. Notes et memoires No 19. 188 records from Suivis scientifiques de la carrière CASEMA "les Communaux" et "la Haie du Maur" à Vatteville-la-Rue (arrêté de dérogation n°SRE/UEP/2013/12/01). 3066 records from Données naturalistes d'Yves BAS. 560 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 1254 records from Inventario forestal en bosques dominados por encino (Quercus Fagaceae) en la Sierra de Manantlán, Jalisco-Colima, México: Descripción de los patrones de respuesta al medio físico y biológico. 4568 records from Monitoreo de la población de la guacamaya verde en la Reserva de la Biosfera Tehuacán-Cuicatlán. 15840 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 42 records from Laophontodes typicus T. Scott (Copepoda, Harpacticoida, Laophontodinae) - discovering a species complex by morphology. 111 records from EPAMA "Vallée de la Meuse"/2006 (Etude ESOPE). 557 records from Étude sur les Mammifères marins de Mayotte entre 2004 et 2008 par l'ONCFS Mayotte, la Collectivité Départementale de Mayotte/Direction de l'Environnement et du Développement Durable, l'Université de la Rochelle et la DAF Mayotte. 2 records from A new species of Lysmata Risso, 1816 (Crustacea, Decapoda, Lysmatidae) from the Gulf of Mexico. 3608 records from (Table 7) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-873B. 318 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 20 records from Données naturalistes d'Olivier BARDET. 354 records from (Appendix) Ostracodes at DSDP Leg 72 Holes. 2455 records from ZUEC-AVE - Coleção de Aves do Museu de Zoologia da UNICAMP. 9 records from Descriptions of larvae of Vestalaria venusta (Hämäläinen, 2004) and Matrona basilaris Selys, 1853 (Odonata: Calopterygidae). 318980 records from Fixed Point Survey for Shorebirds of the family Scolopacidae and Charadriidae. 2832 records from (Table 3) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1012A sediments. 1164 records from Mozambique Endemic and Near-Endemic Red Listed Plant Species. 1462 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 42 records from Cryptochrysa Freitas & Penny, a generic homonym, replaced by Titanochrysa Sosa & Freitas (Neuroptera: Chrysopidae). 16 records from Review of the Genus Ambotingis Drake and Ruhoff (Hemiptera: Heteroptera: Tingidae). 20154 records from Données naturalistes de Nathalie DEVEZEAUX. 67 records from Neostasina gen. nov., a new genus of huntsman spiders from the Neotropical region (Araneae, Sparassidae, Sparianthinae). 234 records from A review of the ant genus Myrmecorhynchus (Hymenoptera: Formicidae). 150 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña noviembre 2006. 222 records from Caracterización ecológica de reptiles presentes en los bosques subxerofíticos de Unguía, Chocó. 74334 records from Environment Agency Rare and Protected Species Records. 40 records from Total evidence analysis of the phylogenetic relationships of bandicoots and bilbies (Marsupialia: Peramelemorphia): reassessment of two species and description of a new species. 3 records from Revision of the genus Allometopon Kertész (Diptera: Clusiidae). 9964 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2007. 2592 records from ConDidact Citizen Science Surveys - Spiders 2014. 139248 records from The Taiwan Roadkill Observation Network Data Set.. 20 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 23 records from Mains of Kinblethmont Solar Park Amphibian Records 2014. 60 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 8 records from Redescription of Micaria beaufortia (Araneae, Gnaphosidae), with notes on Afrotropical Micaria. 2 records from Pelops fuligineus. 18 records from New ants (Hymenoptera: Formicidae) from Micronesia. 9139 records from Composition and distribution of the biomass of zooplankton in the central Arctic Basin 1975, 1976, 1977. 1834 records from The Great Koala Count South Australia. 38 records from Balligratus, new genus of wingless ground beetles from equatorial Andean montane forest (Coleoptera: Carabidae: Lachnophorini). 473934 records from Vogeltrekstation (NL) - Historical Data on Timing of Ringing of Nestling Birds. 10374 records from Satellite tagging of female hawksbill sea turtles (Eretmochelys imbricata) nesting on Groote Eylandt, Northern Territory, 2009-2011. 46711 records from UTEP Fossils (Arctos). 288 records from Amaranthaceae Observations Tanzania and Kenia. 22 records from The cave-dwelling false scorpion genus Pseudoblothrus Beier, 1931 (Arachnida: Pseudoscorpiones: Syarinidae) in the Crimean Peninsula. 235836 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 42 records from Mantodea. 546 records from A taxonomic review of the genus Antepipona de Saussure, 1855 (Hymenoptera: Vespidae: Eumeninae) from India. 12 records from A new species of the genus Takydromus (Squamata: Lacertidae) from Tianjingshan Forestry Station, northern Guangdong, China. 6 records from A systematiC review of the subfamily Syringophilinae (ACari: Syringophilidae) of the NearCtiC region. Part 1: quill mites assoCiated with passerines (Aves: Passeriformes). 49572 records from Nijmegen Natural History Museum (NL) - Entomological Collection. 91374 records from PEUFR - Herbário Professor Vasconcelos Sobrinho. 2 records from Identification of Nipaecoccus (Hemiptera: Coccomorpha: Pseudococcidae) species in the United States, with descriptions of Nipaecoccus bromelicola sp. n. and the male of N. floridensis Beardsley. 24 records from A revision of the clam shrimp Australimnadia Timms and Schwentner, 2012 (Crustacea: Spinicaudata: Limnadiidae) with two new species from Western Australia. 166998 records from The crustaceans collection (IU) of the Muséum national d'Histoire naturelle (MNHN - Paris). 7 records from Speolabeo, a new genus name for the cave fish Bangana musaei (Teleostei: Cyprinidae). 1 records from Live birth in the Devonian period. 44748 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 2 records from Eremaeus oblongus. 32 records from Cryptic diversity in the Azorean beetle genus Tarphius Erichson, 1845 (Coleoptera: Zopheridae): An integrative taxonomic approach with description of four new species. 81 records from Análisis ecológico de la mastofauna en la parte alta del Rio Güangui. 26952 records from Regeneración de especies arbóreas del bosque mesófilo en las montañas del norte de Chiapas. 104 records from Pelvicachromis signatus and Pelvicachromis rubrolabiatus, two new cichlid species (Teleostei, Perciformes) from Guinea, West Africa.. 2 records from Nothrus angulatus. 24 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 34234 records from Catalogue of Afrotropical Bees. 9 records from First record of the genus Echthronomas Forster, 1869 (Hymenoptera, Ichneumonidae, Campopleginae) for the fauna of Ukraine. 86 records from Orthoptera - SMNG. 2584 records from Actualización de bases de datos de invertebrados (Rotifera, Cladocera y Copepoda) y peces. 1994 records from Eastern Mediterranean Syllidae from three locations, in Crete and Israel.. 6 records from Res Ligusticae XXII. Diagnosi di nuove specie di miriapodi cavernicoli. 51 records from Two new species of Nazeris Fauvel in the Luoxiao Mountain Range, China (Coleoptera, Staphylinidae, Paederinae). 2202 records from Monitoreo y seguimiento de fauna terrestre para el AID y AII de la Central Hidroeléctrica de Calima. 2017-B.. 4408 records from Crustacea specimens of Ryukyu University Museum (Fujukan). 45 records from Redescription of the Indo-West Pacific cardinalfishes (Perciformes: Apogonidae) Rhabdamia spilota Allen & Kuiter 1994 and R. gracilis (Bleeker 1856). 14784 record
Keywords: GBIF; biodiversity; species occurrences